Polarization plate, manufacturing method of polarization plate, and display device
The polarizing plate with a polyester and acetyl cellulose film configuration addresses color unevenness and contrast variation in display devices by reducing water absorption and interaction, improving display quality in humid environments.
Patent Information
- Application Number
- JP2023107125
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Polarizing plates in display devices experience color unevenness and contrast variation due to water content, particularly in high-humidity environments, which affect display quality.
A polarizing plate comprising a first optical film made of polyester and a second optical film containing a specific polyester and acetyl cellulose with a degree of acetyl group substitution between 2.30 to 2.80, which suppresses water absorption and interaction with hydrophilic groups, thereby stabilizing the retardation value and contrast.
The solution effectively reduces color unevenness and contrast variation by minimizing water absorption and interaction with acetyl cellulose, enhancing display device performance in humid conditions.
Smart Images

Figure 2025006373000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate, a manufacturing method for a polarizing plate, and a display device. More specifically, the present invention relates to a polarizing plate and the like that suppresses color unevenness and contrast variation due to moisture content. [Background technology]
[0002] In recent years, the environment in which displays (display devices) are used has become increasingly severe. In addition, there is a demand for larger displays and improved display quality, and the demands on displays are increasing. Accordingly, the demands on polarizing plates provided in display devices are also increasing.
[0003] Generally, a polarizing plate is provided with a protective film for protecting the polarizer or the polarizing plate itself, and other functional films.
[0004] Patent Document 1 discloses a technique for a liquid crystal display device having cellulose ester polarizing plate protective films A and B. However, when the liquid crystal display device is stored in a high humidity environment and used in a high humidity environment, or when it is taken out of the high humidity environment and used immediately, there is a problem that color unevenness occurs due to moisture. In addition, there is a problem that the contrast of the display screen of the liquid crystal display device varies. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Korean Patent Publication No. 10-2017-0081024 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in consideration of the above problems and circumstances, and an object of the present invention is to provide a polarizing plate, a manufacturing method for a polarizing plate, and a display device in which color unevenness and contrast variations caused by moisture content are suppressed. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventors have investigated the causes of the above problems and have found that in a polarizing plate comprising a first optical film, a polarizer, and a second optical film, in this order, the first optical film contains a polyester and the second optical film contains a specific polyester and an acetyl cellulose having a degree of substitution of an acetyl group in the range of 2.30 to 2.80, thereby suppressing color unevenness and contrast variations due to moisture content and have arrived at the present invention. That is, the above-mentioned problems of the present invention are solved by the following means.
[0008] 1. A polarizing plate comprising a first optical film, a polarizer, and a second optical film in this order, the first optical film contains polyester, The second optical film contains a polyester represented by the following general formula (I), a polyester represented by the following general formula (II), and an acetyl cellulose having a degree of substitution of an acetyl group in the range of 2.30 to 2.80: A polarizing plate characterized by: General formula (I): T-(DP) n -D General formula (II): T-(DP) n -DT (In the above general formulas (I) and (II), T each represents a benzenecarboxylic acid residue. D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms. P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms, or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms. n represents an integer of 1 or more.
[0009] 2. The content of the polyester represented by the general formula (II) is within the range of 70 to 90% by mass based on the total mass of the polyester represented by the general formula (I) and the polyester represented by the general formula (II). 2. The polarizing plate according to claim 1,
[0010] 3. The polyester contained in the first optical film is polyethylene terephthalate. 2. The polarizing plate according to claim 1,
[0011] 4. The second optical film further contains an ester represented by the following general formula (III): 2. The polarizing plate according to claim 1, General formula (III): TD
[0012] 5. The width of the second optical film is within the range of 2.2 to 3.0 m. 2. The polarizing plate according to claim 1,
[0013] 6. Manufacture of the polarizing plate according to any one of items 1 to 5. The method for producing a polarizing plate according to the present invention comprises the steps of:
[0014] 7. A polarizing plate according to any one of items 1 to 5, The second optical film is disposed on the liquid crystal cell side. A display device comprising: Effect of the Invention
[0015] According to the above-mentioned means of the present invention, it is possible to provide a polarizing plate, a manufacturing method for a polarizing plate, and a display device in which color unevenness and contrast variation due to moisture content are suppressed.
[0016] Although the mechanism by which the effects of the present invention are manifested or the mechanism by which the effects of the present invention are acted upon has not been clearly understood, it is speculated as follows.
[0017] The polarizing plate of the present invention is preferably provided in a display device. In a display device provided with the polarizing plate of the present invention, the first optical film is disposed on the outside compared to the second optical film. Here, "outside" refers to a position in the display device that is closer to the outside air. The second optical film is disposed at a position closer to the liquid crystal cell compared to the first optical film.
[0018] In the conventional technology, when a monochrome image is displayed on a display device stored in a high humidity environment, a uniform monochrome image is not displayed, and color unevenness occurs. Although the cause of the color unevenness is not clear, one of the causes is thought to be in-plane unevenness of the retardation value in the retardation film.
[0019] Acetyl cellulose film is often used as a retardation film. However, in a high humidity environment, water molecules are likely to be coordinated to the hydrophilic groups (carbonyl and hydroxyl groups) of the acetyl cellulose molecule, and the retardation value is likely to fluctuate. Therefore, when a display device having an acetyl cellulose film as a retardation film is stored in a high humidity environment, the performance of the retardation film is deteriorated.
[0020] Large-sized display devices are equipped with acetyl cellulose films having a large area. In a high-humidity environment, the acetyl cellulose film cannot absorb moisture uniformly over the entire surface due to its large area, and the degree of moisture absorption becomes non-uniform within the surface. As a result, the retardation value of the acetyl cellulose film is not uniform over the entire surface, but becomes non-uniform. It is considered that color unevenness occurs when a monochrome image is displayed on such a display device.
[0021] Therefore, it is believed that in a display device, color unevenness due to moisture can be suppressed by reducing the amount of moisture that reaches the acetyl cellulose film. Even if moisture reaches the acetyl cellulose film, it is believed that color unevenness due to moisture can be suppressed by preventing water molecules from coordinating with the carbonyl group or hydroxyl group of the acetyl cellulose molecule.
[0022] The first optical film contains polyester. Polyester has a relatively large number of hydrophobic sites in its chemical structure. Therefore, the first optical film is less likely to absorb moisture, and can suppress moisture from entering the display device. This can reduce the amount of moisture that reaches the second optical film.
[0023] The second optical film contains acetyl cellulose having a degree of substitution of an acetyl group in the range of 2.30 to 2.80. The second optical film also contains polyesters represented by the above general formulas (I) and (II) as additives. In this specification, the polyesters represented by the general formulas (I) and (II) are also referred to as "polyester (I)" and "polyester (II)", respectively.
[0024] Both ends of the polyester (I) are composed of a monocarboxylic acid (T) and a diol (D), respectively. That is, an unreacted hydroxyl group exists at one end of the polyester (I). Hereinafter, such a structure is also referred to as "one-side capped". On the other hand, both ends of the polyester (II) are composed of a monocarboxylic acid (T). That is, there are no unreacted carboxyl or hydroxyl groups at both ends of the polyester (II). Hereinafter, such a structure is also referred to as "double-sided capped".
[0025] The polyesters (I) and (II) are composed of a monocarboxylic acid (T), a diol (D) and a dicarboxylic acid (P). In the monocarboxylic acid (T), the diol (D) and the dicarboxylic acid (P) according to the present invention, the sites other than the carboxyl group and the hydroxyl group are relatively hydrophobic. Therefore, the polyesters (I) and (II) are hydrophobic as compounds. By adding a hydrophobic compound to the acetyl cellulose film, the degree of hydrophobicity of the entire film is improved, and it becomes difficult for the film to absorb moisture.
[0026] The polyester (I) sealed on one side has a hydrophilic hydroxyl group at the end of one side. This hydroxyl group reacts with water molecules that have entered the film. Before the water molecules react with the carbonyl or hydroxyl groups of the acetyl cellulose molecules, they react with the hydroxyl groups of the polyester (I), preventing the acetyl cellulose molecules from reacting with the water molecules. This prevents the film's phase difference from fluctuating.
[0027] From the viewpoint of improving the degree of hydrophobicity of the film, it is preferable to add polyester (II) to seal both sides. However, even if polyester (II) is added, it is difficult to completely prevent moisture from entering the film. Therefore, by adding polyester (I), even if moisture enters the film, the action of water molecules and acetyl cellulose can be suppressed. In other words, by using polyesters (I) and (II) in combination, the fluctuation of the retardation value of the film caused by the action of water molecules and acetyl cellulose can be sufficiently suppressed. As a result, it is considered that color unevenness due to water content can be suppressed.
[0028] In addition, by adding polyesters (I) and (II), the intermolecular distance of acetyl cellulose is increased, and the intermolecular force is weakened. In other words, a plasticizing effect is generated. This allows the entire film to be stretched uniformly in the manufacturing process of the second optical film, and the fast axis or slow axis of the film becomes uniform. As a result, it is believed that the variation in in-plane contrast can be suppressed. Although polyester (I) also generates a sufficient plasticizing effect, polyester (II) generates a higher plasticizing effect. It is believed that a high plasticizing effect can be obtained by using polyesters (I) and (II) in combination.
[0029] In other words, from the viewpoint of improving the hydrophobicity and plasticizing effect of the film, it is considered preferable to add only polyester (II). However, by using polyester (I) in combination, the fluctuation of the retardation value of the film can be sufficiently suppressed. As a result, it is considered that the color unevenness and contrast variation due to water content can be suppressed, and the visibility in the display device can be further improved. [Brief description of the drawings]
[0030] [Figure 1] Cross-sectional diagram of the basic layer structure of a polarizing plate [Diagram 2] FIG. 1 is a schematic diagram showing an example of a configuration of a display device. [Diagram 3] An explanatory diagram of measurement points for evaluating contrast variation DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The polarizing plate of the present invention is a polarizing plate comprising a first optical film, a polarizer, and a second optical film, in this order, characterized in that the first optical film contains a polyester, and the second optical film contains a polyester represented by the above general formula (I), a polyester represented by the above general formula (II), and an acetyl cellulose having a degree of substitution of an acetyl group in the range of 2.30 to 2.80. This feature is a technical feature common to or corresponding to the following embodiments.
[0032] In an embodiment of the present invention, from the viewpoint of improving the hydrophobicity of the second optical film and suppressing color unevenness, it is preferable that the content of the polyester represented by the general formula (II) is within the range of 70 to 90 mass % with respect to the total mass of the polyester represented by the general formula (I) and the polyester represented by the general formula (II).
[0033] In an embodiment of the present invention, from the viewpoint of reducing the amount of moisture that reaches the second optical film and suppressing color unevenness, the polyester contained in the first optical film is preferably polyethylene terephthalate.
[0034] In an embodiment of the present invention, from the viewpoint of preventing water molecules from coordinating with the hydrophilic groups of the acetyl cellulose molecules and suppressing color unevenness, it is preferable that the second optical film further contains an ester represented by the above general formula (III).
[0035] In an embodiment of the present invention, from the viewpoint of achieving both high levels of stretching uniformity and productivity and suppressing variations in contrast, it is preferable that the width of the second optical film is within the range of 2.2 to 3.0 m.
[0036] The method for producing a polarizing plate of the present invention is characterized by producing the above polarizing plate.
[0037] A display device of the present invention includes the above polarizing plate, and the second optical film is disposed on the liquid crystal cell side.
[0038] The present invention, its components, and modes and aspects for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values before and after the symbol "to" are included as the lower limit and upper limit.
[0039] 1. Overview of polarizing plates The polarizing plate of the present invention is a polarizing plate comprising a first optical film, a polarizer, and a second optical film, in this order, characterized in that the first optical film contains a polyester, and the second optical film contains a polyester represented by the following general formula (I), a polyester represented by the following general formula (II), and an acetyl cellulose having a degree of substitution of an acetyl group in the range of 2.30 to 2.80.
[0040] General formula (I): T-(DP) n -D General formula (II): T-(DP) n -DT
[0041] (In the above general formulas (I) and (II), T each represents a benzenecarboxylic acid residue. D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms. P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms, or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms.
[0042] 1 is a cross-sectional view of a basic layer structure of a polarizing plate. The polarizing plate 1 includes a first optical film 2, a polarizer 4, and a second optical film 5 in this order. The polarizing plate 1 may further include any layer, if necessary. For example, another layer may be included between the first optical film 2 and the polarizer 4. Furthermore, another layer may be included between the polarizer 4 and the second optical film 5.
[0043] The first optical film, the second optical film and the polarizer constituting the polarizing plate of the present invention will be described below. The polarizing plate of the present invention may further include known functional layers.
[0044] 2. First Optical Film The first optical film according to the present invention contains polyester. The polyester here is a polyester that is a raw material resin of the film. The first optical film may contain known additives such as an ultraviolet absorbing agent, if necessary.
[0045] The first optical film according to the present invention may have a single-layer structure or a multi-layer structure, and preferably has a multi-layer structure of three or more layers, with an ultraviolet absorbing agent being contained in the intermediate layer.
[0046] From the viewpoint of adhesion to the polarizer, the first optical film preferably has an easy-adhesion layer on at least one side of the film. The easy-adhesion layer preferably contains at least one of polyester resin, polyurethane resin, and polyacrylic resin as a main component. Here, the "main component" refers to a component that occupies 50% by mass or more of the solid components constituting the easy-adhesion layer.
[0047] (1) Polyester The polyester resin used as the raw material has excellent transparency, thermal properties, and mechanical properties, and the retardation value of polyester can be easily controlled by stretching.
[0048] Among them, the polyester is preferably polyethylene terephthalate or polyethylene naphthalate. Polyethylene terephthalate and polyethylene naphthalate have a large inherent birefringence, and therefore, even if the film is thin, a high retardation value can be obtained relatively easily. In particular, the effect of polyethylene naphthalate is remarkable.
[0049] Polyesters can be obtained by condensing any dicarboxylic acid with a diol. Examples of dicarboxylic acids include terephthalic acid, isophthalic acid, orthophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracenedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, and dodecadicarboxylic acid.
[0050] Examples of diols include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone. The dicarboxylic acid component and the diol component may each be contained alone or in combination of two or more.
[0051] Examples of the polyester obtained include polyethylene terephthalate (PET), polypropylene terephthalate, polybutylene terephthalate, polyethylene naphthalate (PEN), etc. Among them, polyethylene terephthalate or polyethylene naphthalate is preferable, and polyethylene terephthalate is more preferable.
[0052] The polyester may contain other copolymer components. From the viewpoint of mechanical strength, the ratio of the copolymer components is preferably 3 mol % or less, more preferably 2 mol % or less, and even more preferably 1.5 mol % or less.
[0053] (2) Ultraviolet absorbers The first optical film preferably contains an ultraviolet absorbing agent. By containing an ultraviolet absorbing agent, the display device can be protected from ultraviolet rays and the weather resistance is excellent. In particular, the alignment film provided in the liquid crystal cell can be protected from ultraviolet rays.
[0054] Examples of the ultraviolet absorbent include cyclic imino ester ultraviolet absorbents, benzotriazole ultraviolet absorbents, benzophenone ultraviolet absorbents, salicylic acid ester ultraviolet absorbents, cyanoacrylate ultraviolet absorbents, and triazine ultraviolet absorbents.
[0055] Examples of cyclic imino ester ultraviolet absorbers include 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one), 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, and 2-phenyl-3,1-benzoxazin-4-one.
[0056] Benzotriazole-based UV absorbers include, for example, 5-chloro-2-(3,5-di-sec-butyl-2-hydroxylphenyl)-2H-benzotriazole. Other benzotriazole-based UV absorbers include, for example, (2-2H-benzotriazol-2-yl)-6-(straight-chain and side-chain dodecyl)-4-methylphenol. Commercially available benzotriazole-based UV absorbers include, for example, the TINUVIN (registered trademark) series, such as "TINUVIN (registered trademark) 109, 171, 234, 326, 327, 328, 928" (all manufactured by BASF).
[0057] Examples of benzophenone-based ultraviolet absorbers include 2-hydroxy-4-benzyloxybenzophenone, 2,4-benzyloxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, and bis(2-methoxy-4-hydroxy-5-benzoylphenylmethane).
[0058] Examples of the salicylic acid ester-based ultraviolet absorbers include phenyl salicylate and p-tert-butyl salicylate. Examples of cyanoacrylate ultraviolet absorbers include 2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, and ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate.
[0059] Examples of triazine-based ultraviolet absorbers include 2-(2'-hydroxy-4'-hexyloxyphenyl)-4,6-diphenyltriazine, etc. Examples of commercially available triazine-based ultraviolet absorbers include "TINUVIN (registered trademark) 477" (manufactured by BASF).
[0060] Among them, the ultraviolet absorbent is more preferably a cyclic imino ester ultraviolet absorbent or a benzotriazole ultraviolet absorbent.
[0061] The content of the ultraviolet absorbing agent is preferably within a range of 0.1 to 10% by mass relative to the total mass of the polyester. When the content is 0.1% by mass or more, the weather resistance of the film is sufficiently obtained. When the content is 10% by mass or less, the transparency of the film is sufficiently obtained. The content of the ultraviolet absorbing agent is more preferably within a range of 0.5 to 10% by mass, and further preferably within a range of 1.5 to 5% by mass, relative to the total mass of the polyester.
[0062] (3) Manufacturing method of the first optical film The first optical film can be manufactured by a known method. Specifically, first, polyester is melted and extruded into a sheet. Then, the formed non-oriented polyester film is stretched in the longitudinal direction by utilizing the speed difference of rollers at a temperature equal to or higher than the glass transition temperature of the film. Thereafter, the polyester film is stretched in the transverse direction by a tenter, and is subjected to a heat treatment and, if necessary, a relaxation treatment. In this way, a stretched polyester film (first optical film) is obtained. The stretched polyester film may be a uniaxially stretched film or a biaxially stretched film.
[0063] The manufacturing conditions for obtaining a polyester film can be appropriately set according to a known method. For example, the longitudinal stretching temperature and the transverse stretching temperature are, for example, within the range of 80 to 130°C, and preferably within the range of 90 to 120°C. The longitudinal stretching ratio is, for example, within the range of 1.0 to 3.5 times, and preferably within the range of 1.0 to 3.0 times. The transverse stretching ratio is, for example, within the range of 2.5 to 6.0 times, and preferably within the range of 3.0 to 5.5 times.
[0064] The retardation value can be controlled by appropriately setting the stretching ratio, stretching temperature or film thickness. For example, the higher the stretching ratio difference between longitudinal stretching and transverse stretching, the lower the stretching temperature, and the thicker the film, the easier it is to increase the retardation value. Conversely, the lower the stretching ratio difference between longitudinal stretching and transverse stretching, the higher the stretching temperature, and the thinner the film, the easier it is to decrease the retardation value.
[0065] Moreover, the higher the stretching temperature and the lower the total stretching ratio, the easier it is to lower the ratio (Ro / Rth) of the retardation value to the thickness direction retardation value. Conversely, the lower the stretching temperature and the higher the total stretching ratio, the easier it is to increase the ratio (Ro / Rth) of the retardation value to the thickness direction retardation value. Details of the retardation value will be described later. The heat treatment temperature is, for example, within the range of 140 to 240°C, and preferably within the range of 170 to 240°C.
[0066] The temperature of the relaxation treatment is, for example, within the range of 100 to 230° C., preferably within the range of 110 to 210° C., and more preferably within the range of 120 to 180° C. The amount of relaxation is, for example, within the range of 0.1 to 20%, preferably within the range of 1 to 10%, and more preferably within the range of 2 to 5%. The temperature and amount of relaxation treatment are preferably set so that the heat shrinkage rate of the polyester film after the relaxation treatment at 150° C. is 2% or less.
[0067] In the uniaxial stretching process and the biaxial stretching process, a heat treatment or a stretching process may be performed again after the transverse stretching. This can alleviate the distortion of the orientation axis due to the bowing phenomenon or the like. The maximum value of the distortion of the orientation axis with respect to the stretching direction due to the bowing phenomenon is preferably within 30°, more preferably within 15°, and even more preferably within 8°. By keeping the maximum value of the distortion of the orientation axis within 30°, the optical properties can be made uniform between sheets when the polarizing plate is manufactured and separated into sheets in the subsequent process.
[0068] Here, the "main axis of orientation" refers to the direction of molecular orientation at any point on the stretched polyester film. The distortion of the main axis of orientation with respect to the stretching direction refers to the angle difference between the main axis of orientation and the stretching direction. Furthermore, the maximum value refers to the maximum value in the direction perpendicular to the longitudinal direction. The main axis of orientation can be measured, for example, using a retardation film and optical material inspection device "RETS" (manufactured by Otsuka Electronics Co., Ltd.) or a molecular orientation meter "MOA" (manufactured by Oji Scientific Instruments Co., Ltd.).
[0069] From the viewpoint of suppressing the fluctuation of the retardation value, it is preferable that the thickness unevenness of the film is small. However, if the longitudinal stretching ratio is lowered to create a difference in the retardation value, the value of the longitudinal thickness unevenness tends to become high. The value of the longitudinal thickness unevenness becomes very high within a certain range of the stretching ratio. Therefore, it is preferable to set the film-forming conditions so that the value of the longitudinal thickness unevenness is outside the certain range. Hereinafter, the longitudinal thickness unevenness is also simply referred to as "thickness unevenness".
[0070] The thickness unevenness is preferably 5.0% or less, more preferably 4.5% or less, even more preferably 4.0% or less, and particularly preferably 3.0% or less.
[0071] The thickness unevenness can be measured by any method. For example, a continuous tape sample (3 m long) is taken in the flow direction of the film. Then, using a commercially available measuring device, the thickness is measured at 100 points at 1 cm intervals, and the maximum thickness (d max ), minimum value (d min ), and the average value (d) is calculated. The thickness unevenness [%] can be calculated using the following formula. An example of a commercially available measuring device is the electronic micrometer "Millitron 1240" (manufactured by Seiko EM Co., Ltd.). (Formula) Thickness unevenness [%] = ((d max -d min ) / d)×100
[0072] The thickness of the stretched polyester film is not particularly limited. The thickness is, for example, within the range of 15 to 300 μm, preferably within the range of 30 to 200 μm, and more preferably within the range of 60 to 80 μm. By being within the above range, it is possible to achieve both thinning and visibility.
[0073] A known method can be used as a method for blending the ultraviolet absorbent. For example, a kneading extruder is used to mix the dried ultraviolet absorbent with polyester raw materials to prepare a master batch. Then, when preparing a film, a predetermined master batch and polyester raw materials are mixed. Here, the term "master batch" refers to a mixture in which the ultraviolet absorbent to be added is blended and kneaded at a high concentration. By using the master batch, the amount of ultraviolet absorbent to be added can be accurately adjusted.
[0074] From the viewpoint of uniformly dispersing the ultraviolet absorbent, the content of the ultraviolet absorbent is preferably within the range of 5 to 30% by mass with respect to the total mass of the master batch. The master batch is preferably produced using a kneading extruder. The extrusion temperature is preferably within the range of the melting point of the polyester raw material or higher and 290°C or lower, and extrusion is preferably performed within the range of 1 to 15 minutes. By setting the extrusion temperature to 290°C or lower, it is possible to suppress the loss of the ultraviolet absorbent and the decrease in the viscosity of the master batch. In addition, by extruding for 1 minute or more, the ultraviolet absorbent can be uniformly dispersed. If necessary, a stabilizer, a color tone adjuster, an antistatic agent, etc. may be added to the master batch.
[0075] A multi-layered film having three or more layers containing an ultraviolet absorber can be manufactured by the following method. For the outer layer, polyester pellets are fed alone to a known melt lamination extruder. For the intermediate layer, a master batch containing an ultraviolet absorber and polyester pellets are mixed in a predetermined ratio, dried, and fed to a known melt lamination extruder. The mixture is extruded into a sheet from a slit die, cooled and solidified on a casting roll, and an unstretched film is obtained. That is, two or more extruders, a three-layer manifold, or a junction block (for example, a junction block having a square junction) are used. Then, the film layers constituting both outer layers and the film layer constituting the intermediate layer are laminated, and a three-layer sheet is extruded from a die and cooled and solidified on a casting roll.
[0076] From the viewpoint of removing foreign matter contained in the polyester raw material, it is preferable to perform high-precision filtration during melt extrusion. The filtration particle size (initial filtration efficiency 95%) of the filter medium used for high-precision filtration is preferably 15 μm or less. By setting the filtration particle size of the filter medium to 15 μm or less, foreign matter of 20 μm or more can be sufficiently removed.
[0077] The easy-adhesion layer can be formed by the following method. The coating liquid used to form the easy-adhesion layer is preferably an aqueous coating liquid containing at least one of water-soluble or water-dispersible copolymer polyester resin, acrylic resin, and polyurethane resin. For these coating liquids, for example, Japanese Patent No. 3567927, Japanese Patent No. 3589232, Japanese Patent No. 3589233, Japanese Patent No. 3900191, Japanese Patent No. 4150982, etc. can be referred to.
[0078] The easy-adhesion layer is obtained by applying a coating liquid to one or both sides of a uniaxially stretched film in the machine direction, drying the film at 100 to 150°C, and stretching the film in the transverse direction. The final coating amount of the easy-adhesion layer is 0.05 to 0.20 g / m 2 It is preferable that the coating amount is within the range of 0.05 g / m 2 By providing the coating amount of 0.20 g / m or more, sufficient adhesion to the polarizer can be obtained. 2 When the thickness is less than 100 nm, sufficient blocking resistance can be obtained. When the easy-adhesion layer is provided on both sides of the polyester film, the coating amount of the easy-adhesion layer on both sides may be the same or different. The coating amount of the easy-adhesion layer on each side can be set within the above range.
[0079] From the viewpoint of easy slipping, the easy-adhesion layer preferably contains particles. The average particle size of the fine particles is preferably 2 μm or less. By having the average particle size of the particles be 2 μm or less, the particles are less likely to fall off from the easy-adhesion layer. Examples of the particles include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride. Other examples of the particles include organic particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be contained alone or in combination of two or more types.
[0080] A known method can be used as a method for applying the coating liquid. Examples of the coating method include reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating. These methods may be used alone or in combination of two or more.
[0081] The average particle size of the above particles can be measured by the following method. Take a photo of the particles using a scanning electron microscope (SEM). Measure the maximum diameter (the distance between the two most distant points) of 300 to 500 particles at a magnification such that the size of the smallest particle is within the range of 2 to 5 mm. Then, take the arithmetic average value as the average particle size.
[0082] (4) Physical Properties of the First Optical Film (4.1) Retardation value The retardation values Ro and Rth of the first optical film are defined by the following formulas, respectively. Formula (i) Ro = (n x -n y )×d Equation (ii) Rth={(n x +n y ) / 2-n z}×d (In the above formulas (i) and (ii), n x represents the refractive index in the direction x where the refractive index is maximum in the in-plane direction of the film. y represents the refractive index in the in-plane direction of the film, in the direction y perpendicular to the direction x. z represents the refractive index in the thickness direction z of the film. d [nm] represents the thickness of the film.
[0083] The retardation value Ro of the first optical film in the in-plane direction for light with a wavelength of 589 nm under an environment of 23° C. and 55% RH is preferably within the range of 3000 to 30000 nm. When Ro is 3000 nm or more, interference colors (rainbow unevenness due to observation angle) when the first optical film is observed from an oblique direction can be reduced, and good visibility can be obtained. In addition, when Ro is 30000 nm or less, the thickness of the film can be reduced. Ro is preferably 5000 nm or more, more preferably 8000 nm or more, and even more preferably 10000 nm or more.
[0084] The retardation value ratio (Ro / Rth) is preferably within the range of 0.2 to 1.2, more preferably within the range of 0.5 to 1.0, and even more preferably within the range of 0.6 to 1.0. By having the ratio value within the above range, rainbow unevenness due to the observation angle of the film can be reduced. The retardation values Ro and Rth can be controlled by the type of polyester, the stretching conditions during film production, etc.
[0085] The retardation values Ro and Rth for light with a wavelength of 589 nm can be measured using an automatic birefringence meter under an environment of 23° C. and 55% RH. Examples of the automatic birefringence meter include the “Axo Scan Mueller Matrix Polarimeter” (manufactured by Axometrics).
[0086] (4.2) Thickness The thickness of the first optical film is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 20 μm or more. By being 5 μm or more, good water resistance and mechanical strength can be obtained. In addition, the thickness of the first optical film is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and particularly preferably 40 μm or less. By being 100 μm or less, both thinness and visibility can be achieved.
[0087] (5) Other functional layers The stretched polyester film may have a functional layer having various properties on at least one surface. Examples of such functional layers include a hard coat layer, an antiglare layer, an antireflection layer, a low reflection layer, a low reflection antiglare layer, an antireflection antiglare layer, an antistatic layer, a silicone layer, an adhesive layer, an antifouling layer, a fingerprint resistant layer, a water repellent layer, and a blue cut layer. From the viewpoint of further improving color spots when observed from an oblique direction, the functional layer is preferably an antiglare layer, an antireflection layer, a low reflection layer, a low reflection antiglare layer, or an antireflection antiglare layer.
[0088] When providing various functional layers, it is preferable to provide an easy-adhesion layer on the surface of the stretched polyester film. In this case, from the viewpoint of suppressing interference due to reflected light, it is preferable to adjust the refractive index of the easy-adhesion layer so that it is close to the geometric mean of the refractive index of the functional layer and the refractive index of the stretched polyester film. The refractive index of the easy-adhesion layer can be adjusted by a known method. For example, the refractive index can be easily adjusted by adding titanium, zirconium or other metal species to the binder resin of the easy-adhesion layer.
[0089] The coating liquid used for forming the easy-adhesion layer preferably contains at least water-soluble or water-dispersible copolymer polyester, acrylic resin or polyurethane. Examples of the coating liquid include water-soluble or water-dispersible copolymer polyester solutions, acrylic resin solutions, polyurethane solutions, etc. described in JP-B-6-81714, JP-B-3200929, JP-B-3632044, JP-B-4547644, JP-B-4770971, JP-B-3567927, JP-B-3589232, JP-B-3589233, JP-B-3900191, JP-B-4150982, etc.
[0090] 3. Second Optical Film The second optical film according to the present invention contains polyester (I), polyester (II), and acetyl cellulose having a degree of acetyl group substitution in the range of 2.30 to 2.80.
[0091] (1) Polyester additives The second optical film according to the present invention contains polyesters (I) and (II). Hereinafter, polyesters (I) and (II) are collectively referred to as "polyester additives". By containing the polyester additives in the second optical film, color unevenness and contrast variation due to water content can be suppressed in the polarizing plate.
[0092] (1.1) Structure of polyester additives The polyesters (I) and (II) are represented by the following general formulas (I) and (II). General formula (I): T-(DP) n -D General formula (II): T-(DP) n -DT
[0093] In the general formulae (I) and (II), T each represents a benzenecarboxylic acid residue. D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms. P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms, or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms. n represents an integer of 1 or more.
[0094] In the repeating structure of general formula (I), n D's and P's may all be the same structure or different structures. In the repeating structure of general formula (II), n D's and P's may all be the same structure or different structures. In general formula (I), D in the repeating structure and D at the terminal may be the same structure or different structures. In general formula (II), D in the repeating structure and D at the terminal may be the same structure or different structures. In general formula (II), T at both ends may have the same structure or different structures.
[0095] T, D, and P in general formula (I) and T, D, and P in general formula (II) may have the same structure or different structures. In addition, n in general formula (I) and n in general formula (II) may have the same value or different values. However, it is preferable that the structure of polyester (I) is the same as the structure of polyester (II) except for one end (T). By similarity of the structures of polyester (I) and polyester (II), their compatibility is improved, and the effect of the present invention can be obtained remarkably.
[0096] In the present invention, the "residue" in the benzenecarboxylic acid residue, alkylene glycol residue, arylene glycol residue, oxyalkylene glycol residue, alkylenedicarboxylic acid residue, and arylene dicarboxylic acid residue refers to the structure of the remaining portion excluding a hydroxy group or a hydrogen atom that is lost in the molecular structural formula when, for example, a benzenecarboxylic acid, an alkylene glycol, or the like forms an ester. That is, when a monocarboxylic acid is represented as "R-COOH", the monocarboxylic acid residue is represented as "R-CO-". When a dicarboxylic acid is represented as "HOOC-R-COOH", the dicarboxylic acid residue is represented as "-OC-R-CO-". When a glycol (diol) is represented as "HO-R-OH", the glycol (diol) residue is represented as "-ORO-" or "-OR-OH".
[0097] Each T represents a benzene carboxylic acid residue. Examples of the benzene carboxylic acid include orthotoluic acid, metatoluic acid, paratoluic acid, benzoic acid, para-tertiary butyl benzoic acid, dimethyl benzoic acid, ethyl benzoic acid, normal propyl benzoic acid, amino benzoic acid, and acetoxy benzoic acid. Among them, the benzene carboxylic acid is preferably toluic acid. These may be contained alone or in combination of two or more.
[0098] D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms.
[0099] Examples of alkylene glycols having 2 to 12 carbon atoms include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,2-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2,2-diethyl-1,3-propanediol, and the like. Examples of the diol include 3,3-dimethylol pentane, 2-n-butyl-2-ethyl-1,3-propane diol, 3,3-dimethylol heptane, 3-methyl-1,5-pentane diol, 1,6-hexane diol, 2,2,4-trimethyl-1,3-pentane diol, 2-ethyl-1,3-hexane diol, 2-methyl-1,8-octanediol, 1,9-nonane diol, 1,10-decane diol, and 1,12-octadecane diol. Among these, propylene glycol or neopentyl glycol is preferred. These may be contained alone or in combination of two or more.
[0100] Examples of the arylene glycol having a carbon number in the range of 6 to 12 include 1,2-dihydroxybenzene (catechol), 1,3-dihydroxybenzene (resorcinol), and 1,4-dihydroxybenzene (hydroquinone). These may be contained alone or in combination of two or more.
[0101] Examples of the oxyalkylene glycol having a carbon number in the range of 4 to 12 include diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, etc. Among these, diethylene glycol, triethylene glycol, or dipropylene glycol is preferable. These may be contained alone or in combination of two or more.
[0102] P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms, or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms.
[0103] Examples of the alkylene dicarboxylic acid having 4 to 12 carbon atoms include succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid. These may be contained alone or in combination of two or more.
[0104] Examples of the arylene dicarboxylic acid having a carbon number in the range of 6 to 12 include phthalic acid, terephthalic acid, isophthalic acid, 1,5-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, etc. Among these, phthalic acid is preferable. These may be contained alone or in combination of two or more.
[0105] Each n represents the number of repetitions, and is preferably within the range of 1 to 170.
[0106] The number average molecular weight of the polyester is preferably 20,000 or less, more preferably 10,000 or less. Among them, polyester additives having a number average molecular weight in the range of 400 to 10,000 have good compatibility with acetyl cellulose. In addition, polyester additives having a number average molecular weight in the range of 400 to 10,000 are preferable because they are less likely to evaporate or vaporize during film formation. The number average molecular weight of the polyester can be measured by gel permeation chromatography (GPC). For low molecular weight compounds that cannot be measured by GPC, the number average molecular weight can be calculated from the structural formula.
[0107] The polyester preferably has an acid value of 0.5 mgKOH / g or less, more preferably 0.3 mgKOH / g or less, and a hydroxyl value of 25 mgKOH / g or less, more preferably 15 mgKOH / g or less.
[0108] "Acid value" refers to the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of sample. "Hydroxyl value" refers to the number of milligrams of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of sample is acetylated. Acid value and hydroxyl value can be measured in accordance with JIS K0070.
[0109] Specific examples of polyester (II) are shown below. However, the present invention is not limited thereto. It is preferable that polyester (I) and ester (III) described later have the same structures as T, D, and P in polyester (II) described below.
[0110] [ka]
[0111] [ka]
[0112] [ka]
[0113] [ka]
[0114] (1.2) Synthesis method of polyester additives Polycondensation of polyester is not particularly limited, and known methods can be used. For example, direct reaction of dicarboxylic acid with diol can be mentioned. In addition, thermal melt condensation method by polyesterification reaction or ester exchange reaction between dicarboxylic acid or its alkyl ester (e.g., methyl ester) and diol can be mentioned. In addition, dehydrohalogenation reaction between acid chloride of dicarboxylic acid and diol can be mentioned.
[0115] It is preferable to synthesize polyesters with a low number average molecular weight by direct reaction. Polyesters with a high distribution rate on the low molecular weight side have high compatibility with acetyl cellulose. The second optical film formed has low moisture permeability and excellent transparency.
[0116] The method for adjusting the molecular weight is not particularly limited, and a known method can be used. For example, when the ends of the molecule are blocked with a monocarboxylic acid, the molecular weight can be adjusted by controlling the amount of monocarboxylic acid added. In addition, by controlling the amount of monocarboxylic acid added, it is possible to select one-side blocking or both-side blocking.
[0117] From this viewpoint, it is preferable that the monocarboxylic acid is one which is not distilled out of the system during the polycondensation reaction but is easily distilled out of the reaction system when the reaction is terminated. Also, a mixture of a monocarboxylic acid which is difficult to distill out of the system during the polycondensation reaction and a monocarboxylic acid which is easy to distill out of the reaction system when the reaction is terminated may be used.
[0118] In the case of a direct reaction, the number average molecular weight can be adjusted by timing the termination of the reaction based on the amount of water distilled off during the polycondensation reaction. In addition, the number average molecular weight can be adjusted by biasing the number of moles of the dicarboxylic acid or diol to be charged. The number average molecular weight can also be adjusted by controlling the reaction temperature.
[0119] As an example, a method for synthesizing compound A in which only one end of the molecule is capped with a monocarboxylic acid is shown below.
[0120] [ka]
[0121] (Synthesis of intermediate 1) The following ingredients are dissolved in ethyl acetate: Propylene glycol 228.0 parts by mass Triethylamine 121.0 parts by mass While maintaining the temperature of the reaction mixture below 50°C, add the following components: Terephthalic acid chloride 101.5 parts by mass
[0122] After the addition is complete, the reaction solution is stirred at room temperature for 5 hours. Water is added to the reaction solution, the mixture is stirred, and the aqueous layer is removed. The organic layer is further washed with water four times. The solvent in the organic layer is distilled off under reduced pressure to obtain intermediate 1 (127 parts by mass, 90% yield).
[0123] (Synthesis of compound P11) The following components are dissolved in toluene: Intermediate 1 71.5 parts by mass Triethylamine 30.0 parts by mass While maintaining the temperature of the reaction mixture below 50°C, add the following components: p-Toluic acid chloride 19.3 parts by mass
[0124] After the addition is complete, the reaction solution is stirred at room temperature for 5 hours. Water is added to the reaction solution, and the solution is stirred, and the aqueous layer is removed. The organic layer is further washed twice with a 5% aqueous sodium carbonate solution. The organic layer is washed with saturated saline and then concentrated under reduced pressure. The resulting residue is purified by silica gel column chromatography to obtain compound A (37.5 parts by mass, 75% yield).
[0125] (1.3) Polyester additive content The total content of the polyester additives is preferably within a range of 1 to 40 mass %, more preferably within a range of 2 to 30 mass %, and even more preferably within a range of 3 to 15 mass %, relative to the total mass of the second optical film.
[0126] The content of polyester (II) is preferably within a range of 70 to 90% by mass based on the total mass of polyester (I) and polyester (II). By being within the above range, color unevenness due to water content can be further suppressed.
[0127] (1.4) Low molecular weight esters The second optical film according to the present invention preferably contains an ester (III), which is represented by the following general formula (III).
[0128] General formula (III): TD In addition, T and D in the general formula (III) have the same meanings as T and D in the general formulae (I) and (II) above.
[0129] The structure of polyester (III) is preferably the same as the structure of polyester (I) excluding the repeating unit. The similarity of the structures of polyester (I) and polyester (III) improves their compatibility, and the effects of the present invention can be significantly achieved.
[0130] The content of the ester (III) is preferably within a range of 0.1 to 10 mass %, more preferably within a range of 0.2 to 8 mass %, and further preferably within a range of 0.3 to 5 mass %, relative to the total mass of the second optical film.
[0131] The relationship between the polyester (I), the polyester (II) and the ester (III) is shown below. Water resistance: Ester (III) < Polyester (I) < Polyester (II) Plasticizing effect: Ester (III) < Polyester (I) < Polyester (II) Ease of movement: Polyester (II) < Polyester (I) < Ester (III)
[0132] In these compounds, the higher the ratio of hydrophobic sites to hydrophilic sites in the molecule, the more hydrophobic the molecule is and the higher the water resistance effect. By containing a compound with high water resistance effect, moisture is less likely to be taken into the film, and the retardation value of the film is less likely to fluctuate.
[0133] The larger the molecular weight of these compounds, the higher the plasticizing effect. By containing a compound having a high plasticizing effect in a film, the film can be stretched uniformly, and the fast axis or slow axis of the film can be made uniform.
[0134] The smaller the molecular weight of these compounds, the more easily they can move within the film. When the film contains a compound that has a hydrophilic group and is easily mobile, water molecules are coordinated to the compound first, preventing water molecules from coordinating to the hydrophilic group of the acetyl cellulose molecule. In other words, by further containing the ester (III), coordination of water molecules with the hydrophilic groups of the acetyl cellulose molecules can be further prevented, and fluctuations in the retardation value of the film can be further suppressed.
[0135] (2) Cellulose acetate Cellulose is a polymer in which β-glucose units are linked in a straight chain by β-1,4-glycosidic bonds. Cellulose ester is cellulose in which some or all of the hydrogen atoms in the hydroxyl groups (-OH) at the 2nd, 3rd, and 6th positions in one glucose unit are replaced with acyl groups. Cellulose ester in which the acyl group is an acetyl group is called "acetyl cellulose."
[0136] The degree of substitution of the acetyl group in the acetyl cellulose according to the present invention is within the range of 2.30 to 2.80. The degree of substitution is preferably within the range of 2.40 to 2.70. When the degree of substitution is within the above range, a desired retardation value can be obtained.
[0137] (Degree of acetyl substitution) The degree of acetyl substitution refers to the average number of acetyl groups per glucose unit, i.e., how many of the hydrogen atoms of the hydroxyl groups at positions 2, 3, and 6 in one glucose unit are substituted with acetyl groups. Therefore, the maximum degree of substitution of the acetyl group is 3.0, which means that all of the hydrogen atoms of the hydroxy groups at the 2-, 3- and 6-positions are substituted with acetyl groups.
[0138] The acetyl groups may be substituted evenly at the 2-, 3- and 6-positions of one glucose unit, or may be substituted with a distribution. The degree of acetyl substitution can be determined by the method specified in ASTM-D817-96.
[0139] From the viewpoint of obtaining desired optical properties, acetyl celluloses having different degrees of substitution may be mixed and used. The mixing ratio of acetyl celluloses having different degrees of substitution is not particularly limited.
[0140] From the viewpoint of mechanical strength, the number average molecular weight (Mn) of acetyl cellulose is 2×10 4 ~3×10 5 It is preferable that the range is 2×10 4 ~1.2×10 5More preferably, it is within the range of 4×10 4 ~8×10 4 It is more preferable that the ratio is within the range of 1.
[0141] From the viewpoint of mechanical strength, the weight-average molecular weight (Mw) of acetyl cellulose is 2×10 4 ~1×10 6 It is preferable that the range is 2×10 4 ~1.2×10 5 More preferably, it is within the range of 4×10 4 ~8×10 4 It is more preferable that the ratio is within the range of 1. The number average molecular weight (Mn) and weight average molecular weight (Mw) of acetyl cellulose can be measured by the following method.
[0142] <Gel permeation chromatography> Solvent: Methylene chloride Column: Shodex K806, K805, K803G (all manufactured by Showa Denko K.K.) connected together Column temperature: 25℃ Sample concentration: 0.1% by mass Detector: RI Model 504 (GL Sciences) Pump: L6000 (Hitachi, Ltd.) Flow rate: 1.0mL / min Calibration curve: A calibration curve was used using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) in the range of Mw=500 to 2,800,000. It is preferable to use the 13 samples at approximately equal intervals.
[0143] Acetyl cellulose can be synthesized by a known method.
[0144] The raw cellulose for acetyl cellulose is not particularly limited, and examples thereof include cotton linters, wood pulp, and kenaf. The raw cellulose, acetic acid, acetic anhydride, and a catalyst (such as sulfuric acid) are mixed together to esterify the cellulose. The reaction is continued until a cellulose triester is produced. In the triester, all of the hydrogen atoms of the three hydroxyl groups in one glucose unit are substituted with acetyl groups.
[0145] The triester of cellulose is then hydrolyzed to give acetyl cellulose having the desired degree of acetyl group substitution. Thereafter, acetyl cellulose is finally obtained through steps such as filtration, precipitation, washing with water, dehydration, drying, etc. Specifically, it can be synthesized with reference to the method described in JP-A-10-45804.
[0146] Commercially available acetyl cellulose products include "LM80, L20, L30, L40, L50" (all manufactured by Daicel Corporation), "Ca398-3, Ca398-6, Ca398-10, Ca398-30, Ca394-60S" (all manufactured by Eastman Chemical Company), and the like.
[0147] (3) Other additives The second optical film may further contain additives as necessary. Examples of additives include sugar esters, acrylic polymers, plasticizers, fine particles, etc. The second optical film may also contain the above-mentioned ultraviolet absorbing agent.
[0148] (3.1) Sugar esters The second optical film contains a sugar ester, which makes it possible to adjust the retardation value of the film.
[0149] Examples of sugar esters include compounds in which all or a part of the hydroxy groups (-OH) in a compound (A) having one furanose structure or pyranose structure are esterified with aliphatic acyl groups. Examples of sugar esters include compounds in which all or a part of the hydroxyl groups (-OH) in a compound (B) having at least one of furanose structures or pyranose structures bonded within the range of 2 to 12 units are esterified with aliphatic acyl groups.
[0150] Preferred examples of the compound (A) and the compound (B) include the compounds shown below, but the present invention is not limited thereto.
[0151] Examples of the compound (A) include glucose, galactose, mannose, fructose, xylose, arabinose, etc. The compound (A) also includes maltitol, which is obtained by hydrogenating and reducing maltose under high pressure. Examples of the compound (B) include lactose, sucrose, cellobiose, maltose, cellotriose, maltotriose, raffinose, and kestose. Among them, the compound preferably has both a furanose structure and a pyranose structure. An example of a compound having both a furanose structure and a pyranose structure is sucrose.
[0152] The monocarboxylic acid used in synthesizing the sugar ester is not particularly limited, and examples thereof include known aliphatic monocarboxylic acids, alicyclic monocarboxylic acids, etc. The monocarboxylic acid may be used alone or in combination of two or more kinds.
[0153] Examples of aliphatic monocarboxylic acids include saturated fatty acids such as acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, 2-ethyl-hexanecarboxylic acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, and lacteric acid; and unsaturated fatty acids such as undecylenic acid, oleic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, and octenic acid.
[0154] Examples of the alicyclic monocarboxylic acid include cyclopentane carboxylic acid, cyclohexane carboxylic acid, cyclooctane carboxylic acid, and derivatives thereof.
[0155] For the synthesis of these compounds, see, for example, JP-A-8-245678.
[0156] As the sugar ester, an esterified compound of an oligosaccharide in which at least one of furanose structures or pyranose structures is bonded within the range of 3 to 12 units can also be used.
[0157] Oligosaccharides are produced by reacting starch, sucrose, etc. with an enzyme such as amylase. Examples of oligosaccharides include maltooligosaccharides, isomaltooligosaccharides, fructooligosaccharides, galactooligosaccharides, and xylooligosaccharides. Oligosaccharides can also be acetylated in the same manner as the above-mentioned compounds (A) and (B).
[0158] An example of the synthesis of sugar ester is shown below. Pyridine (100 mL) is added to glucose (29.8 g, 166 mmol) to prepare a solution. Acetic anhydride (200 mL) is added dropwise to this solution and reacted for 24 hours. After that, the solution is concentrated by evaporation, and the concentrate is poured into ice water. The concentrate is left for 1 hour, and then filtered through a glass filter to separate the solid from the water. The solid on the glass filter is dissolved in chloroform, and the solution is separated with cold water until it becomes neutral. After separating the organic layer, the organic layer is dried with anhydrous sodium sulfate. After removing the anhydrous sodium sulfate from the organic layer by filtration, the chloroform is removed by evaporation. The remaining reaction product is further dried under reduced pressure to obtain glucose pentaacetate (58.8 g, 150 mmol, 90.9%). Note that the above monocarboxylic acid can be used instead of the above acetic anhydride.
[0159] Specific examples of sugar ester compounds applicable to the present invention are given below, but the present invention is not limited thereto.
[0160] [ka]
[0161] [ka]
[0162] [ka]
[0163] [ka]
[0164] [ka]
[0165] The sugar ester content is preferably within a range of 1 to 35% by mass, more preferably within a range of 5 to 30% by mass, based on the total mass of the second optical film. By being within the above range, deterioration of the polarizing function of the polarizing plate can be suppressed, and the display quality of the display device can be stabilized. In addition, even if the raw material of the second optical film is stored in a rolled laminated state, bleeding out is unlikely to occur.
[0166] A sugar ester in which all OH groups have been esterified may be used in combination with a sugar ester in which one or more OH groups remain. Examples of the sugar esters used in combination include a mixture of sucrose octaacetate, sucrose heptaacetate, and sucrose hexaacetate. The mixing ratio is not particularly limited, and examples of the combinations include 30:30:30, 40:30:30, 40:50:10, 50:30:20, 60:30:10, 80:10:10, 90:7:3, and 95:5:0. The mixing ratio can be controlled by adjusting the reaction time during esterification of sugar or the amount of monocarboxylic acid added to react with sugar.
[0167] (3.2) Acrylic polymer The second protective film contains an acrylic polymer, which allows the retardation value of the film to be adjusted. The number average molecular weight of the acrylic polymer is preferably within a range of 500 to 30000. For such an acrylic polymer, reference can be made to paragraphs
[0059] to
[0093] of WO 2008 / 044463.
[0168] (3.3) Plasticizers The second optical film contains a plasticizer, so that the entire film is stretched uniformly, and the fast axis or slow axis of the film becomes uniform. As a result, the in-plane contrast variation in the display device can be suppressed. In addition, the second optical film contains a plasticizer, so that the retardation value can be adjusted.
[0169] The plasticizer is not particularly limited, and examples thereof include polycarboxylic acid ester plasticizers, glycolate plasticizers, phthalate ester plasticizers, fatty acid ester plasticizers, polyhydric alcohol ester plasticizers, polyester plasticizers, and acrylic plasticizers.
[0170] The glycolate-based plasticizer is not particularly limited, but is preferably an alkylphthalyl alkyl glycolate.As the alkylphthalyl alkyl glycolate, for example, methylphthalyl methyl glycolate, ethylphthalyl ethyl glycolate, propylphthalyl propyl glycolate, butylphthalyl butyl glycolate, octylphthalyl octyl glycolate, methylphthalyl ethyl glycolate, ethylphthalyl methyl glycolate, ethylphthalyl propyl glycolate, methylphthalyl butyl glycolate, ethylphthalyl butyl glycolate, butylphthalyl methyl glycolate, butylphthalyl ethyl glycolate, propylphthalyl butyl glycolate, butylphthalyl propyl glycolate, methylphthalyl octyl glycolate, ethylphthalyl octyl glycolate, octylphthalyl methyl glycolate, octylphthalyl ethyl glycolate, etc. can be mentioned.
[0171] Examples of phthalate plasticizers include diethyl phthalate, dimethoxyethyl phthalate, dimethyl phthalate, dioctyl phthalate, dibutyl phthalate, di-2-ethylhexyl phthalate, dioctyl phthalate, dicyclohexyl phthalate, and dicyclohexyl terephthalate.
[0172] Examples of the citrate plasticizer include acetyl trimethyl citrate, acetyl triethyl citrate, and acetyl tributyl citrate.
[0173] Examples of fatty acid ester plasticizers include butyl oleate, methylacetyl ricinoleate, and dibutyl sebacate.
[0174] Examples of the phosphate plasticizer include triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, diphenyl biphenyl phosphate, trioctyl phosphate, and tributyl phosphate.
[0175] (3.3.1) Polycarboxylic acid ester plasticizers Examples of polycarboxylic acid esters include esters of alcohols and polycarboxylic acids having a valence of 2 or more, preferably 2 to 20. The valence of the polycarboxylic acid is preferably within the range of 2 to 20 for aliphatic polycarboxylic acids, and preferably within the range of 3 to 20 for aromatic polycarboxylic acids and alicyclic polycarboxylic acids.
[0176] The polycarboxylic acid is represented by the following general formula (IV).
[0177] General formula (IV): R2(COOH) m (OH) n In the above general formula (IV), R2 represents an (m+n)-valent organic group, m represents a positive integer of 2 or more, n represents an integer of 0 or more, the COOH group represents a carboxy group, and the OH group represents an alcoholic or phenolic hydroxy group.
[0178] The polycarboxylic acid is not particularly limited, and examples thereof include aromatic polycarboxylic acids having 3 or more valences or derivatives thereof (e.g., trimellitic acid, trimesic acid, pyromellitic acid), aliphatic polycarboxylic acids (e.g., succinic acid, adipic acid, azelaic acid, sebacic acid, oxalic acid, fumaric acid, maleic acid, tetrahydrophthalic acid), oxypolycarboxylic acids (e.g., tartaric acid, tartronic acid, malic acid, citric acid), etc. Among them, from the viewpoint of improving retention, oxypolycarboxylic acids are preferable.
[0179] In a high temperature and high humidity environment, additives such as plasticizers are likely to precipitate or volatilize outside the film, and as a result, the mass of the film is likely to decrease. In the present invention, "retention" refers to the property of suppressing the precipitation or volatilization of additives outside the film and allowing the additives to remain within the film. Specifically, the mass of a sample is measured after being left for one day in an environment of 23°C and 55% RH. Next, the sample is left for two weeks in an environment of 80°C and 90% RH, and the mass of this sample is measured after being left for one day at 23°C and 55% RH. The ratio of change in mass of these samples is calculated and used as a measure of retention. It can be determined that the smaller the ratio of change in mass, the higher the retention.
[0180] The alcohol is not particularly limited, and examples thereof include known alcohols or phenols. Examples of the alcohol include aliphatic saturated alcohols or aliphatic unsaturated alcohols having a straight chain or a side chain with a carbon number of 1 to 32. The carbon number is preferably within the range of 1 to 20, and more preferably within the range of 1 to 10. Examples of the alcohol include alicyclic alcohols (cyclopentanol, cyclohexanol, etc.) or derivatives thereof, aromatic alcohols (benzyl alcohol, cinnamyl alcohol, etc.) or derivatives thereof, etc. The alcohols may be used alone or in combination of two or more.
[0181] When an oxypolycarboxylic acid is used as the polycarboxylic acid, the alcoholic or phenolic hydroxy group of the oxypolycarboxylic acid may be esterified with a monocarboxylic acid. The monocarboxylic acid is not particularly limited, and examples thereof include the following.
[0182] Examples of the aliphatic monocarboxylic acid include fatty acids having a straight or branched chain and a carbon number in the range of 1 to 32. The carbon number is preferably in the range of 1 to 20, and more preferably in the range of 1 to 10.
[0183] Examples of aliphatic monocarboxylic acids include saturated fatty acids (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, 2-ethyl-hexanecarboxylic acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, and lacteric acid), and unsaturated fatty acids (undecylenic acid, oleic acid, sorbic acid, linoleic acid, linolenic acid, and arachidonic acid).
[0184] Examples of the alicyclic monocarboxylic acid include cyclopentane carboxylic acid, cyclohexane carboxylic acid, cyclooctane carboxylic acid, and derivatives thereof.
[0185] Examples of aromatic monocarboxylic acids include benzoic acid, benzoic acid having an alkyl group introduced into the benzene ring (toluic acid, etc.), aromatic monocarboxylic acids having two or more benzene rings (biphenylcarboxylic acid, naphthalenecarboxylic acid, tetralincarboxylic acid, etc.), and derivatives thereof. Of these, the monocarboxylic acid is preferably acetic acid, propionic acid or benzoic acid.
[0186] The molecular weight of the polyvalent carboxylate ester is not particularly limited, but is preferably within the range of 300 to 1000, and more preferably within the range of 350 to 750. From the viewpoint of improving retention, a larger molecular weight is preferable, and from the viewpoints of moisture permeability and compatibility with acetyl cellulose, a smaller molecular weight is preferable.
[0187] The acid value of the polycarboxylic acid ester is preferably 1 mgKOH / g or less, more preferably 0.2 mgKOH / g or less. By having the acid value within the above range, environmental fluctuation of the retardation value can be suppressed.
[0188] Examples of polycarboxylic acid esters are shown below, but the present invention is not limited thereto. Examples of polycarboxylic acid esters include triethyl citrate, tributyl citrate, acetyl triethyl citrate (abbreviation: ATEC), acetyl tributyl citrate (abbreviation: ATBC), benzoyl tributyl citrate, acetyl triphenyl citrate, acetyl tribenzyl citrate, dibutyl tartrate, diacetyl dibutyl tartrate, tributyl trimellitate, and tetrabutyl pyromellitate.
[0189] (3.4) Fine particles The second protective film contains fine particles, which can improve the slipperiness of the film surface. In addition, when the films are stacked, scratches and adhesion between the films can be suppressed. In the present invention, the "fine particles" refer to particles having an average primary particle size in the range of 5 to 400 nm.
[0190] The fine particles may be inorganic fine particles or organic fine particles. Examples of inorganic fine particles include silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, talc, clay, calcined kaolin, etc. Examples of inorganic fine particles include calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc. From the viewpoint of reducing turbidity, it is preferable that the inorganic fine particles contain silicon, and among them, silicon dioxide is preferable.
[0191] The silicon dioxide fine particles may be commercially available products, such as Aerosil (registered trademark) R972, R972V, R974, R812, 200, 200V, 300, R202, OX50, and TT600 (all manufactured by Nippon Aerosil Co., Ltd.).
[0192] Commercially available zirconium oxide particles may be used, such as Aerosil (registered trademark) R976 and R811 (both manufactured by Nippon Aerosil Co., Ltd.).
[0193] Examples of the polymer constituting the organic fine particles include silicone resin, fluororesin, and acrylic resin. Among them, the polymer is preferably a silicone resin, and more preferably a silicone resin having a three-dimensional network structure. Commercially available products may be used as the silicone resin fine particles. Examples of commercially available products include "Tospearl (registered trademark) 103, 105, 108, 120, 145, 3120, and 240" (all manufactured by Toshiba Silicone Co., Ltd.).
[0194] Among them, the fine particles are preferably "Aerosil (registered trademark) 200V" or "Aerosil (registered trademark) R972V". By containing these fine particles, the coefficient of friction can be sufficiently reduced while maintaining the turbidity of the second optical film low. The dynamic friction coefficient of at least one surface of the second optical film is preferably within a range of 0.2 to 1.0.
[0195] The average particle size of the primary particles of the fine particles is preferably within the range of 10 to 300 nm. The fine particles may be contained as secondary aggregates having a particle size within the range of 0.05 to 0.3 μm. Particles having an average particle size within the range of 100 to 400 nm are preferably contained as primary particles without being aggregated.
[0196] The content of the fine particles is preferably within a range of 0.01 to 1 mass %, and more preferably within a range of 0.05 to 0.5 mass %, based on the total mass of the second optical film.
[0197] (4) Method for manufacturing the second optical film The method for producing the second optical film may be a solution casting method or a melt casting method, of which the solution casting method is preferred.
[0198] The film production method by the solution casting method includes the steps of preparing a dope, casting the dope onto a metal support, drying the web, and peeling the film from the metal support. The film production method by the solution casting method also includes the steps of stretching or width-holding the peeled film, further drying the film, and winding up the finished film.
[0199] (4.1) Preparation of dope In the step of preparing the dope, the dope is prepared by dissolving acetyl cellulose and additives in a solvent. The concentration of acetyl cellulose in the dope is preferably high because it reduces the drying load after casting onto the metal support. In addition, by not increasing the concentration of acetyl cellulose too much, the pressure load during filtration can be suppressed, and good filtration accuracy can be obtained. From these viewpoints, the content of acetyl cellulose is preferably within the range of 10 to 35% by mass, more preferably within the range of 15 to 25% by mass, based on the total mass of the dope.
[0200] The solvent used in the preparation of the dope may be one type alone or two or more types. However, from the viewpoint of production efficiency, it is preferable to mix a good solvent and a poor solvent for acetyl cellulose, and from the viewpoint of the solubility of acetyl cellulose, it is preferable to have a large amount of good solvent. The mixing ratio of the good solvent to the poor solvent is preferably within the range of 70 to 98 mass % of the good solvent, and preferably within the range of 2 to 30 mass % of the poor solvent. A solvent that dissolves acetyl cellulose alone is defined as a "good solvent", and a solvent that swells or does not dissolve acetyl cellulose alone is defined as a "poor solvent".
[0201] The good solvent is not particularly limited, and examples thereof include organic halogen compounds (e.g., methylene chloride), dioxolanes, acetone, methyl acetate, methyl acetoacetate, etc. Among them, methylene chloride or methyl acetate is preferable. The poor solvent is not particularly limited, and examples thereof include methanol, ethanol, n-butanol, cyclohexane, cyclohexanone, etc.
[0202] The dope preferably contains water in the range of 0.01 to 2% by mass. The solvent used to dissolve acetyl cellulose may be removed from the film by drying and recovered, and reused. The recovered solvent may contain a trace amount of additives (e.g., plasticizers, ultraviolet absorbers, polymers, monomer components, etc.). The recovered solvent can be reused even if it contains additives. The recovered solvent may be purified, if necessary, and reused.
[0203] When preparing the dope, the method of dissolving acetyl cellulose can be a known method. For example, by combining a heating means and a pressurizing means, the dope can be heated to a temperature above the boiling point at normal pressure. By stirring and dissolving acetyl cellulose while heating the solvent at a temperature above the boiling point at normal pressure and within a range in which the solvent does not boil under pressure, the generation of lumpy undissolved matter (gel or solids) can be prevented. In addition, acetyl cellulose may be mixed with a poor solvent to wet or swell it, and then a good solvent may be added to dissolve it.
[0204] The pressurization method includes a method of injecting an inert gas such as nitrogen gas into a dissolution vessel, a method of increasing the vapor pressure of the solvent by heating, etc. Heating is preferably performed from the outside, and for example, a jacket type is preferable because it is easy to control the temperature.
[0205] From the viewpoint of the solubility of acetyl cellulose, a higher heating temperature is preferable. Moreover, by not setting the heating temperature too high, the pressure load can be suppressed, and good productivity can be obtained. From these viewpoints, the heating temperature is preferably within the range of 45 to 120°C, more preferably within the range of 60 to 110°C, and even more preferably within the range of 70°C to 105°C. The pressure is adjusted so that the solvent does not boil at the set temperature.
[0206] Another method for dissolving acetyl cellulose is the cooling dissolution method, which can dissolve acetyl cellulose in a solvent such as methyl acetate.
[0207] The acetyl cellulose solution is filtered using a suitable filter material such as filter paper. From the viewpoint of removing insoluble matters, the filter material preferably has a small absolute filtration accuracy. Moreover, by not making the absolute filtration accuracy too small, clogging of the filter material can be suppressed. From these viewpoints, the absolute filtration accuracy of the filter material is preferably 0.008 mm or less, more preferably within the range of 0.001 to 0.008 mm, and even more preferably within the range of 0.003 to 0.006 mm.
[0208] The material of the filter material is not particularly limited, and known filter materials can be used. The filter material is preferably made of plastic (polypropylene, Teflon (registered trademark), etc.) or metal (stainless steel, etc.) from the viewpoint of preventing fiber from falling off. By filtering, impurities contained in the raw material acetyl cellulose, particularly bright spot foreign matter, can be removed or reduced.
[0209] Two polarizing plates are placed in a crossed Nicol state, and a second optical film is placed between them. Light is applied from one polarizing plate side and observed from the other polarizing plate side. At this time, any spots that appear to be leaking light from the opposite side are called "bright spot foreign matter." The number of bright spots with a diameter of 0.01 mm or more is 200 / cm 2 It is preferable that the number of particles is less than 100 / cm. 2 The number of bright spots with a diameter of 0.01 mm or more is preferably 50 / cm. 2 More preferably, it is 0 to 10 particles / cm or less. 2 It is particularly preferable that the number of bright spots having a diameter of 0.01 mm or less is small.
[0210] The dope can be filtered by a known method. Among them, a method of filtering the dope while heating the solvent at a temperature that is equal to or higher than the boiling point at normal pressure and does not boil the solvent under pressure is preferred. In this method, the increase in the difference in filtration pressure (differential pressure) before and after filtration is small. The heating temperature is preferably within a range of 45 to 120°C, more preferably within a range of 45 to 70°C, and even more preferably within a range of 45 to 55°C.
[0211] The filtration pressure is preferably smaller, and is preferably 1.6 MPa or less, more preferably 1.2 MPa or less, and even more preferably 1.0 MPa or less.
[0212] The various additives may be added in batches or in-line by preparing a separate additive solution. In particular, when fine particles are added to the dope, it is preferable to add a part or the whole of the additives in-line in order to reduce the load of the fine particles on the filter material.
[0213] When the additive solution is added in-line, it is preferable to add a small amount of acetyl cellulose to the additive solution and dissolve it in order to improve the mixing property with the dope. The amount of acetyl cellulose added is preferably within the range of 1 to 10% by mass, more preferably within the range of 3 to 5% by mass, based on the total mass of the solvent.
[0214] In-line addition and mixing can be carried out using, for example, a static mixer, an in-line mixer, etc. Examples of static mixers include those manufactured by Toray Engineering Co., Ltd. Examples of in-line mixers include the Toray static in-pipe mixer "Hi-Mixer SWJ" (manufactured by Toray Engineering Co., Ltd.).
[0215] (4.2) Casting the dope onto a metal support In the step of casting the dope onto the metal support, the dope is cast onto an endless metal support that moves indefinitely. The metal support in the casting step is preferably one with a mirror-finished surface. The metal support is preferably a stainless steel belt or a cast drum with a plated surface. The width of the cast is preferably within the range of, for example, 1 to 4 m.
[0216] (4.3) Drying the web In the step of drying the web, the dope cast onto the metal support is dried as a web. The surface temperature of the metal support is preferably in the range of -50°C or higher and lower than the boiling point of the solvent. The higher the surface temperature, the faster the drying speed of the web can be. Also, by not raising the surface temperature too high, foaming of the web can be prevented and good flatness of the film can be obtained. From these viewpoints, the surface temperature is preferably in the range of 0 to 40°C, and more preferably in the range of 5 to 30°C. Also, the metal support may be cooled to gel the web, and the film may be peeled off from the drum in a state in which it contains a large amount of residual solvent.
[0217] The method for controlling the temperature of the metal support is not particularly limited, and examples thereof include a method of blowing hot or cold air onto the metal support. Another example is a method of bringing hot water into contact with the back side of the metal support. The method using hot water can shorten the time until the temperature of the metal support becomes constant because heat is efficiently transferred. When hot air is used, air having a higher temperature than the target temperature of the metal support may be used.
[0218] (4.4) Peeling the film off the metal support From the viewpoint of obtaining good flatness of the film, the residual solvent amount when peeling the film (web) from the metal support is preferably within the range of 10 to 150% by mass. The residual solvent amount is more preferably within the range of 10 to 40% by mass or 60 to 130% by mass, and further preferably within the range of 10 to 30% by mass or 70 to 120% by mass. Here, the residual solvent amount is defined by the following formula.
[0219] Residual solvent amount [mass%] = {(MN) / N} x 100 where M is the mass of the web or film sample, and N is the mass of the web or film sample after heating at 115° C. for 1 hour. Note that the web or film sample can be taken at any time during or after production.
[0220] (4.5) Step of stretching or width-holding the peeled film In the process of stretching or width-holding the peeled film, the film with a large amount of residual solvent immediately after peeling is stretched or width-held. It is preferable to use a tenter method in which the film is stretched in the conveying direction (longitudinal direction) and then both ends of the film are held by clips or the like. It is also possible to stretch the film in the conveying direction (longitudinal direction) and width direction (lateral direction) simultaneously.
[0221] In the longitudinal stretching, the peel tension is preferably 210 N / m or more, and more preferably within the range of 220 to 300 N / m.
[0222] The stretching process allows the refractive index of the film to be controlled, and the retardation values Ro and Rth to be controlled.
[0223] The final stretching ratio is preferably within the range of 1.0 to 2.0 times in the conveying direction, and more preferably within the range of 1.01 to 1.5 times, and the final stretching ratio is preferably within the range of 1.01 to 2.5 times in the width direction, and more preferably within the range of 1.05 to 2.0 times.
[0224] The method of stretching the film is not particularly limited. For example, the stretching method includes a method in which a plurality of rollers are provided with different peripheral speeds, and the film is stretched in the longitudinal direction by utilizing the roller peripheral speed difference between them. The stretching method includes a method in which both ends of the film are fixed with clips or pins, and the interval between the clips or pins is expanded in the conveying direction, and the film is stretched in the longitudinal direction. Similarly, the method in which the interval between the clips or pins is expanded in the width direction, and the film is stretched in the transverse direction, is also included. Similarly, the method in which the interval between the clips or pins is expanded simultaneously in the conveying direction and the width direction, and the film is stretched in both the longitudinal and transverse directions is also included.
[0225] These stretching methods may be used in combination. In the case of a tenter system, if the clip portion is driven by a linear drive system, the film can be stretched smoothly and the risk of the film breaking can be reduced.
[0226] The width holding or transverse stretching is preferably carried out by a tenter system, and may be performed using either a pin tenter or a clip tenter.
[0227] If the fast axis or slow axis of the film exists in the film plane and the angle it forms with the transport direction is θ1, then θ1 is preferably within the range of -0.5 to +0.5°, more preferably within the range of -0.3 to +0.3°, and even more preferably within the range of -0.2 to +0.2°. This θ1 can be defined as the orientation angle. θ1 can be measured using an automatic birefringence meter "KOBRA-21ADH" (Oji Scientific Instruments). By having θ1 within the above range, high brightness can be obtained in the displayed image. In addition, light leakage can be suppressed or prevented, and colors can be faithfully reproduced in a color liquid crystal display device.
[0228] (4.6) Further drying of the film In the step of further drying the film, the peeled film is further dried. The drying may be performed after or simultaneously with the stretching. The residual solvent content of the film after drying is preferably 1% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.01% by mass or less.
[0229] The drying method is not particularly limited, and examples thereof include a roller drying method in which the film is dried by passing it alternately between multiple rollers arranged above and below. Alternatively, the film may be dried while being stretched by the tenter method.
[0230] The means for drying the film is not particularly limited, and examples thereof include hot air, infrared rays, a heating roller, microwaves, etc. From the viewpoint of simplicity, the drying means is preferably hot air.
[0231] The drying temperature is preferably increased stepwise within the range of 40 to 200° C. From the viewpoint of dimensional stability, the drying temperature is more preferably within the range of 50 to 140° C.
[0232] (4.7) Winding up the finished film The finished film is preferably stored, for example, in a roll.
[0233] (5) Physical properties of the second optical film (5.1) Retardation value The retardation value Ro is preferably within a range of 30 to 90 nm. The retardation value Rth is preferably within a range of 100 to 200 nm. By setting the retardation value within the above range, light leakage can be suppressed when a liquid crystal display device including the polarizing plate of the present invention is viewed from an oblique direction.
[0234] (5.2) Thickness The thickness of the film is preferably within the range of 10 to 200 μm, more preferably within the range of 10 to 60 μm, and further preferably within the range of 10 to 40 μm.
[0235] (5.3) Width The width of the film is preferably in the range of 1 to 4 m, more preferably in the range of 1.3 to 4 m, and further preferably in the range of 2.2 to 3.0 m. By having the width in the range of 2.2 to 3.0 m, both uniformity of stretching and productivity can be achieved at a high level.
[0236] 4. Polarizer In the present invention, the term "polarizer" refers to an element that transmits only light with a certain polarization plane, or a layer that includes the element. An example of the polarizer is a polyvinyl alcohol polarizing film. Polyvinyl alcohol polarizing films include those dyed with iodine and those dyed with a dichroic dye.
[0237] A method for producing a polarizer includes forming a film from an aqueous polyvinyl alcohol solution, uniaxially stretching the film, and dyeing the film. After dyeing, the film may be uniaxially stretched and subjected to durability treatment with a boron compound or the like.
[0238] The thickness of the polarizer is preferably within the range of 2 to 30 μm, and more preferably within the range of 2 to 20 μm.
[0239] Examples of polyvinyl alcohol include ethylene-modified polyvinyl alcohols described in JP-A-2003-248123 and JP-A-2003-342322. The ethylene-modified polyvinyl alcohol has an ethylene unit content in the range of 1 to 4 mol%, a polymerization degree in the range of 2000 to 4000, and a saponification degree in the range of 99.0 to 99.99 mol%. Among them, ethylene-modified polyvinyl alcohols having a hot water cutting temperature in the range of 66 to 73° C. are preferred. This ethylene-modified polyvinyl alcohol polarizing film has excellent polarization performance and durability, has little color unevenness, and is particularly preferably used for large liquid crystal display devices.
[0240] 5. Manufacturing method of polarizing plate The polarizing plate of the present invention can be produced by a general method. The surface of the first protective film of the present invention facing the polarizer is appropriately treated, and the film is attached to at least one surface of the polarizer produced by immersing the film in an iodine solution and stretching the film, using an ultraviolet-curable adhesive or a water-based adhesive, which will be described later. A second protective film is attached to the other surface of the polarizer in the same manner.
[0241] The direction of lamination with the polarizer is preferably such that, for example, the absorption axis of the polarizer and the slow axis of each protective film are perpendicular to each other.
[0242] (1) UV-curable adhesive The polarizing plate of the present invention is preferably produced by bonding the optical film and the polarizer with an ultraviolet-curable adhesive. By using an ultraviolet-curable adhesive, a polarizing plate having high strength and excellent flatness even though it is thin can be obtained.
[0243] (1.1) Composition of UV-curable adhesive Examples of the ultraviolet-curable adhesive composition for polarizing plates include a photoradical polymerization type composition utilizing photoradical polymerization and a photocationic polymerization type composition utilizing photocationic polymerization. Examples of the ultraviolet-curable adhesive composition for polarizing plates include a hybrid type composition utilizing both photoradical polymerization and photocationic polymerization.
[0244] An example of a photoradical polymerization composition is the composition described in JP 2008-009329 A. This composition contains a radical polymerizable compound containing a polar group such as a hydroxy group or a carboxy group, and a radical polymerizable compound not containing a polar group, in a specific ratio.
[0245] The radical polymerizable compound contained in the photoradical polymerization composition is preferably a compound having a radically polymerizable ethylenically unsaturated bond.The compound having a radically polymerizable ethylenically unsaturated bond may be, for example, a compound having a (meth)acryloyl group.The compound having a (meth)acryloyl group may be, for example, an N-substituted (meth)acrylamide compound, a (meth)acrylate compound, etc.
[0246] In addition, the term "(meth)acryloyl group" refers to an acryloyl group or a methacryloyl group, the term "(meth)acrylate" refers to an acrylate or a methacrylate, and the term "(meth)acrylamide" refers to an acrylamide or a methacrylamide.
[0247] An example of a photocationic polymerization composition is the composition described in JP 2011-028234 A. The composition contains (α) a cationic polymerizable compound, (β) a photocationic polymerization initiator, (γ) a photosensitizer that exhibits maximum absorption at wavelengths longer than 380 nm, and (δ) a naphthalene-based photosensitizer assistant. Examples of the cationic polymerizable compound include an epoxy compound and an oxetane compound. The ultraviolet-curing adhesive is not limited to these, and any known adhesive can be used.
[0248] (2) Manufacturing method of polarizing plate After the optical film and the polarizer are pretreated, an ultraviolet-curable adhesive is applied to them. Next, the optical film and the polarizer are bonded together via the ultraviolet-curable adhesive. Then, the ultraviolet-curable adhesive is cured.
[0249] (2.1) Pretreatment process In the pretreatment step, the adhesion surfaces of the optical film and the polarizer are subjected to an adhesion enhancing treatment, such as a corona treatment or a plasma treatment.
[0250] (2.2) Coating process In the coating step, the ultraviolet-curable adhesive is applied to at least one of the adhesive surfaces between the optical film and the polarizer. When the ultraviolet-curable adhesive is directly applied to the surface of the optical film or the polarizer, the coating method is not limited. Examples of the coating method include a doctor blade, a wire bar, a die coater, a comma coater, a gravure coater, etc., and various wet coating methods can be used. In addition, after the ultraviolet-curable adhesive is applied between the optical film and the polarizer, pressure may be applied with a roller or the like to uniformly spread the ultraviolet-curable adhesive.
[0251] (2.3) Lamination process In the lamination step, when an ultraviolet-curable adhesive is applied to the surface of the polarizer in the previous application step, the optical film is superimposed on the ultraviolet-curable adhesive, and when an ultraviolet-curable adhesive is applied to the surface of the optical film, the polarizer is superimposed on the ultraviolet-curable adhesive.
[0252] When the ultraviolet-curing adhesive is cast between the optical film and the polarizer, the optical film and the polarizer are superimposed in this state. Usually, in this state, the optical film is pressed by sandwiching the optical film side with pressure rollers or the like. Examples of the material of the pressure roller include metal and rubber. The pressure rollers arranged on both sides may be made of the same material or different materials.
[0253] (2.4) Curing process In the curing step, the applied ultraviolet-curable adhesive is irradiated with ultraviolet light. Then, the ultraviolet-curable adhesive is cured to bond the optical film and the polarizer that are superimposed via the ultraviolet-curable adhesive. In the present invention, optical films that are light-transmitting are superimposed on both sides of the polarizer, respectively, via ultraviolet-curable adhesives. In this state, it is preferable to irradiate with ultraviolet light and simultaneously cure the ultraviolet-curable adhesives on both sides.
[0254] The conditions for the ultraviolet irradiation are not particularly limited as long as they are conditions that allow the ultraviolet-curing adhesive to be cured. The amount of ultraviolet irradiation is 50 to 1500 mJ / cm2 in terms of cumulative light amount. 2It is preferable that the range is 100 to 500 mJ / cm 2 In the present invention, it is preferable to irradiate with ultraviolet light from the second optical film side, from the viewpoint of improving yield.
[0255] When the polarizing plate is manufactured on a continuous line, the line speed is preferably within the range of 1 to 500 m / min, more preferably within the range of 5 to 300 m / min, and even more preferably within the range of 10 to 100 m / min. By setting the line speed to 1 m / min or more, productivity can be ensured. In addition, damage to the optical film can be suppressed, and a polarizing plate having excellent durability can be obtained. By setting the line speed to 500 m / min or less, the ultraviolet-curable adhesive can be sufficiently cured. An adhesive layer having the desired hardness and excellent adhesiveness can be formed. The line speed is preferably adjusted in consideration of the curing time of the adhesive.
[0256] 6.Display device The display device of the present invention is characterized in that it includes the polarizing plate and the second optical film is disposed on the liquid crystal cell side. By including the polarizing plate, color unevenness and contrast variation due to moisture can be suppressed.
[0257] The polarizing plate of the present invention can be used in liquid crystal display devices of various driving modes such as STN, TN, OCB, HAN, VA (MVA, PVA), IPS, OCB, etc. Among them, it is preferably used in IPS type liquid crystal display devices.
[0258] In a liquid crystal display device, two polarizing plates are usually used, one on the viewing side and the other on the backlight side. The polarizing plate of the present invention may be used as both polarizing plates or as one of the polarizing plates. For the direction of lamination of the polarizing plates in an IPS type liquid crystal display device, for example, JP-A-2005-234431 can be referred to.
[0259] The liquid crystal cell according to the present invention comprises a liquid crystal layer and a pair of substrates sandwiching the liquid crystal layer. From the viewpoint of making the display device thinner and lighter, the pair of substrates are preferably glass substrates having a thickness within a range of 0.3 to 0.7 mm.
[0260] FIG. 2 is a schematic cross-sectional view showing an example of the configuration of a display device (100) in which polarizing plates (101A and 101B) of the present invention are arranged on both sides of a liquid crystal cell (101C).
[0261] 2, a liquid crystal cell (101C) is formed by sandwiching both sides of a liquid crystal layer (107) between glass substrates (108A and 108B) as transparent base materials. Polarizing plates (101A and 101B) are arranged on the respective surfaces of the glass substrates (108A and 108B) via adhesive layers (106), thereby forming a display device (100).
[0262] In the polarizing plates (101A and 101B), a first optical film is attached to positions 102A and 102B, and a second optical film is attached to positions 105A and 105B. The optical films are attached to polarizers (104A and 104B) by ultraviolet-curing adhesives (103A to 103D), respectively.
[0263] The liquid crystal cell (101C) includes an alignment film, a transparent electrode, and glass substrates (108A and 108B) on both sides of the liquid crystal material. Examples of materials for the glass substrate include soda-lime glass and silicate glass. Among them, silicate glass is preferable, and more specifically, silica glass or borosilicate glass is more preferable.
[0264] The glass constituting the glass substrate is preferably an alkali-free glass that does not substantially contain an alkali component. Specifically, the content of the alkali component in the glass substrate is preferably 1000 ppm or less. The content of the alkali component in the glass substrate is more preferably 500 ppm or less, and even more preferably 300 ppm or less. By using an alkali-free glass that does not substantially contain an alkali component, it is possible to suppress soda blowing caused by the replacement of cations on the optical film surface. This makes it possible to suppress a decrease in density on the optical film surface, and to prevent damage to the glass substrate.
[0265] The glass substrate can be produced by a known method, such as a float method, a down-draw method, an overflow down-draw method, etc. Among them, the overflow down-draw method is preferred because the surface of the glass substrate does not come into contact with a forming member during forming, and the surface of the obtained glass substrate is less likely to be scratched.
[0266] The glass substrate may be a commercially available product. Examples of commercially available glass substrates include "AN100" (thickness 500 μm, manufactured by Asahi Glass Co., Ltd.), "EAGLE XG(r) Slim" (thickness 300 μm, 400 μm, etc., manufactured by Corning Incorporated), and glass base material (thickness within the range of 100 to 200 μm, manufactured by Nippon Electric Glass Co., Ltd.).
[0267] As shown in FIG. 2, the polarizing plates (101A, 101B) and the liquid crystal cell (101C) are bonded together via an adhesive layer (106). Examples of the adhesive layer include a layer formed using a double-sided tape, an ultraviolet-curable adhesive, and the like. Examples of the double-sided tape include a substrate-less tape "MO-3005C" (thickness 25 μm, manufactured by Lintec Corporation). There are no particular limitations on the bonding method, and known methods can be used.
[0268] In addition to the effects of the present invention, the liquid crystal display device of the present invention has excellent interlayer adhesion, resistance to fading, resistance to egg-like unevenness in displayed images, etc. By using the polarizing plate of the present invention, a liquid crystal display device that has excellent visibility, is thin, and is lightweight, even for a large screen of 30 inches or more, can be obtained. EXAMPLES
[0269] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified. In the following examples, operations were carried out at room temperature (25° C.) unless otherwise specified.
[0270] 1. Preparation of Polarizing Plates (1) Preparation of the First Optical Film First optical films (optical films Nos. 1 and 2) were prepared according to the following method.
[0271] (1.1) Preparation of Optical Film 1 (1.1.1) Synthesis of polyester A The temperature of the esterification reactor was raised, and when it reached 200°C, the following components were added. Terephthalic acid 86.400 parts by mass Ethylene glycol 64.600 parts by mass
[0272] While stirring the mixture, the following catalyst was added to the esterification reactor, and the pressurized esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and a temperature of 240°C. Antimony trioxide 0.017 parts by mass Magnesium acetate tetrahydrate 0.064 parts by mass Triethylamine 0.160 parts by mass
[0273] The esterification reactor was then returned to atmospheric pressure and the following components were added: Phosphoric acid 0.014 parts by mass The reaction mixture was then heated to 260° C. over 15 minutes, and the following components were added to the esterification reactor: Trimethyl phosphate 0.012 parts by mass
[0274] After 15 minutes, the reaction product was dispersed using a high-pressure disperser, and after another 15 minutes, the reaction product was transferred to a polycondensation reactor and subjected to a polycondensation reaction at 280° C. under reduced pressure.
[0275] After the polycondensation reaction was completed, the reaction product was filtered using a "Naslon (registered trademark) filter NF-05S" (95% cut diameter: 5 μm, manufactured by Nippon Seisen Co., Ltd.). The reaction product was extruded in the form of strands from a nozzle. The reaction product was then cooled using cooling water that had been previously filtered (pore diameter: 1 μm or less), solidified, and cut into pellets. The intrinsic viscosity of the resulting polyester A (polyethylene terephthalate: PET) was 0.62 dL / g. The polyester was substantially free of inert particles and internally precipitated particles.
[0276] (1.1.2) Preparation of polyester B The dried ultraviolet absorbent and the above polyester A were mixed in the ratio shown below, and a polyester B containing the ultraviolet absorbent was obtained using a kneading extruder.
[0277] Ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) 10 parts by mass Polyester A 90 parts by weight
[0278] (1.1.3) Preparation of adhesive modification coating solution Using the components listed below, transesterification and polycondensation were carried out by known methods to prepare a water-dispersible copolymer polyester resin containing a metal sulfonate salt group.
[0279] The dicarboxylic acid components were mixed in the following ratios relative to the total dicarboxylic acid components. Terephthalic acid 46 mol% Isophthalic acid 46 mol% Sodium 5-sulfonatoisophthalate 8 mol% The glycol components were mixed in the following proportions relative to the total glycol components: Ethylene glycol 50 mol% Neopentyl glycol 50 mol%
[0280] The following ingredients were then mixed: Water 51.40 parts by mass Isopropyl alcohol 38.00 parts by weight n-Butyl cellosolve 5.00 parts by mass Nonionic surfactant 0.06 parts by weight
[0281] The mixture was then heated and stirred, and when the temperature reached 77°C, the following components were added. Stirring was continued until no resin lumps remained, and the resin water dispersion was then cooled to room temperature to obtain a uniform water-dispersible copolymerized polyester resin solution with a solid content concentration of 5.0 mass%. 5.00 parts by mass of the above copolymer polyester resin
[0282] The following components were dispersed to prepare an aqueous dispersion of silica particles. Aggregated silica particles "Silysia 310" (manufactured by Fuji Silysia Co., Ltd.) 3.00 parts by mass Water 50.00 parts by mass
[0283] The following ingredients were mixed: The above water-dispersible copolymer polyester resin liquid: 99.46 parts by mass Silica particle water dispersion 0.54 parts by weight While stirring the mixture, the following components were added to obtain an adhesion modifying coating liquid. Water 20.00 parts by mass
[0284] (1.1.4) Formation of Optical Film 1 Pellets of the following polyester were dried at 135°C for 6 hours under reduced pressure of 133.3 Pa (1 Torr), and then fed to extruder 2 (for intermediate layer II). Then, the pellets were melted at 285°C. Polyester A 90 parts by weight Polyester B 10 parts by weight
[0285] The polyester A synthesized above was dried by a conventional method, fed to extruder 1 (for outer layer I and outer layer III), and melted at 285°C.
[0286] These molten polyesters were each filtered with a stainless steel sintered filter medium (nominal filtration accuracy 10μm particle cut 95%). Then, they were laminated in a two-kind three-layer merging block, and extruded into a sheet from a die. Then, using an electrostatic casting method, the extruded polyester was wrapped around a casting drum with a surface temperature of 30℃ and cooled to solidify. Then, an unstretched polyester film (PET film) was obtained. The discharge rate of each extruder was adjusted so that the thickness ratio of the I layer, II layer, and III layer was 10:80:10.
[0287] Next, a coating of 0.08 g / m2 was applied to both sides of the unstretched polyester film by the reverse roll method. 2 The adhesiveness-modifying coating liquid was applied so that the thickness of the coated layer became 10 mm. Thereafter, the coating liquid was dried at 80° C. for 20 seconds.
[0288] The unstretched polyester film was introduced into a tenter stretching machine, and while the ends of the film were held by clips, it was stretched 4.0 times in the width direction in a hot air zone at a temperature of 125°C. Next, the film was treated at a temperature of 225°C for 30 seconds while maintaining the width stretched in the width direction. Furthermore, the film was subjected to a relaxation treatment of 3% in the width direction. Thus, an optical film 1 having a thickness of 50 μm and uniaxial orientation was obtained.
[0289] (1.2) Preparation of Optical Film 2 Optical film 2 was obtained in the same manner as in the preparation of optical film 1, except that triacetyl cellulose (TAC) was used instead of polyester.
[0290] (2) Preparation of the second optical film The second optical films (optical films Nos. 3 to 17) were prepared according to the following method.
[0291] (2.1) Preparation of Optical Film 3 First, the details of the acetyl cellulose and polyester additive used in the preparation of the second optical film will be described below.
[0292] (cellulose acetate) Acetyl cellulose 1 (AC1): acetyl substitution degree 2.50 Acetyl cellulose 2 (AC2): acetyl substitution degree 2.20 Acetyl cellulose 3 (AC3): acetyl substitution degree 2.40 Acetyl cellulose 4 (AC4): acetyl substitution degree 2.60 Acetyl cellulose 5 (AC5): acetyl substitution degree 2.70 Acetyl cellulose 6 (AC6): acetyl substitution degree 2.90
[0293] (Additives) The structural formula of the additive is shown below. For compounds P11 and P21, the value of n was 1, and for compounds P12 and P22, the value of n was 2.
[0294] [ka]
[0295] (2.1.1) Synthesis of additives (2.1.1.1) Synthesis of compound P11 The reaction scheme for synthesizing compound P11 from terephthalic acid chloride is shown below.
[0296] [ka]
[0297] (Synthesis of intermediate 1) The following ingredients were dissolved in ethyl acetate: Propylene glycol 228.0 parts by mass Triethylamine 121.0 parts by mass While maintaining the temperature of the reaction solution at 50° C. or less, the following components were added. Terephthalic acid chloride 101.5 parts by mass
[0298] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution, and the mixture was stirred, and the aqueous layer was removed. The organic layer was further washed with water four times. The solvent in the organic layer was distilled off under reduced pressure, and 127 parts by mass of intermediate 1 was obtained (yield 90%).
[0299] (Synthesis of compound P11) The following components were dissolved in toluene: Intermediate 1 71.5 parts by mass Triethylamine 30.0 parts by mass While maintaining the temperature of the reaction solution at 50° C. or less, the following components were added. p-Toluic acid chloride 19.3 parts by mass
[0300] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution, and the mixture was stirred, and the aqueous layer was removed. The organic layer was further washed twice with a 5% aqueous sodium carbonate solution. The organic layer was washed with saturated saline and then concentrated under reduced pressure. The resulting residue was purified by silica gel column chromatography to obtain 37.5 parts by mass of compound P11 (yield 75%).
[0301] (2.1.1.2) Synthesis of compound P21 Compound P21 was obtained in the same manner as in the synthesis of compound P11, except that the amount of p-toluic acid chloride added was changed to 38.6 parts by mass.
[0302] (2.1.1.3) Synthesis of compound P31 The following ingredients were dissolved in ethyl acetate: Propylene glycol 228.0 parts by mass Triethylamine 121.0 parts by mass While maintaining the temperature of the reaction solution at 50° C. or less, the following components were added. p-Toluic acid chloride 19.3 parts by mass
[0303] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution, and the mixture was stirred, and the aqueous layer was removed. The organic layer was further washed with water four times. The solvent in the organic layer was distilled off under reduced pressure to obtain compound P31 (yield 90%).
[0304] (2.1.2) Preparation of dope <Fine particle dispersion> The following components were mixed and stirred for 50 minutes in a dissolver, and then dispersed in a Manton-Gaulin to obtain a fine particle dispersion. Fine particles "Aerosil (registered trademark) R812" (manufactured by Nippon Aerosil Co., Ltd.) 11.0 parts by mass Ethanol 89.0 parts by mass
[0305] <Fine particle additive liquid> Acetyl cellulose with a degree of substitution of 2.40 was added to a dissolution tank containing methylene chloride and heated to completely dissolve. This solution was then filtered using "Azumi Filter Paper No. 244" (manufactured by Azumi Filter Paper Co., Ltd.). The filtered acetyl cellulose solution was stirred thoroughly while the above-mentioned microparticle dispersion was slowly added thereto. The mixture was then dispersed using an attritor so that the secondary particles had a specified particle size. The resulting dispersion was filtered using "Finemet NF" (manufactured by Nippon Seisen Co., Ltd.) to prepare a microparticle-added solution. Methylene chloride 99.0 parts by mass Acetyl cellulose 4.0 parts by mass Fine particle dispersion liquid 11.0 parts by mass
[0306] Next, a main dope solution having the following composition was prepared.
[0307] First, methylene chloride and ethanol were added to a pressurized dissolution tank. Acetyl cellulose with a degree of substitution of 2.40 was added to the pressurized dissolution tank containing the solvent while stirring. This was heated and stirred until it was completely dissolved. Two more additives were added to the solution and dissolved. The solution was filtered using "Azumi Filter Paper No. 244" (manufactured by Azumi Filter Paper Co., Ltd.) to prepare the main dope solution.
[0308] <Composition of main dope> Methylene chloride 300.0 parts by mass Ethanol 30.0 parts by mass Acetyl cellulose 100.0 parts by mass Compound P11 5.0 parts by mass Compound P21 5.0 parts by mass
[0309] 2 parts by mass of the microparticle additive liquid was added to 100.0 parts by mass of the main dope liquid, and mixed thoroughly with an in-line mixer (Toray static type pipe mixer) "Hi-Mixer, SWJ" (manufactured by Toray Engineering Co., Ltd.) to prepare a dope. The content of compound P11 in the dope was 5% by mass relative to the mass of acetyl cellulose. Similarly, the content of compound P21 was 5% by mass relative to the mass of acetyl cellulose.
[0310] (2.1.3) Formation of Optical Film 3 The dope prepared above was uniformly cast on a stainless steel belt with a width of 2 m at 22°C using a belt casting apparatus. The solvent in the web was evaporated on the stainless steel belt until the residual solvent amount was less than 100%. Then, the film was peeled off from the stainless steel belt with a peeling tension of 160 N / m.
[0311] Next, the solvent was evaporated from the peeled film at 35° C., and the film was slit. Thereafter, the film was stretched in the width direction (TD direction) at 1.6 times the original width using a tenter stretching machine at a temperature of 160° C. The amount of residual solvent in the film when stretching by the tenter was started was 3 to 15 mass %.
[0312] The film was then dried while being conveyed by multiple rollers in drying zones at 120° C. and 140° C. The film was slit into a width of 2.5 m, and knurling was applied to both ends of the film to a width of 10 mm and a height of 2.5 μm. The film was then wound around a core to obtain an optical film 3 having a thickness of 40 μm and a winding length of 3,900 m.
[0313] (2.2) Preparation of Optical Films 4 to 17 Optical Films 4 to 17 were obtained in the same manner as in the preparation of Optical Film 3, except that the type of resin and the type and content of additives were changed as shown in Table I. The thickness of each of Optical Films 4 to 17 was 40 μm.
[0314] (3) Preparation of polarizer A long polyvinyl alcohol film with a thickness of 60 μm was prepared. While the film was continuously transported via a guide roller, the film was immersed in a dye bath (30°C) containing iodine and potassium iodide for dyeing treatment, and the film was stretched 2.5 times. After that, the film was stretched 5 times in total and crosslinked in an acid bath (60°C) containing boric acid and potassium iodide. The obtained iodine-PVA polarizer film with a thickness of 12 μm was dried in a dryer at 50°C for 30 minutes. Then, a polarizer with a moisture content of 4.9% was obtained.
[0315] (4) Preparation of polarizing plates (4.1) Preparation of polarizing plate 1 A polarizing plate 1 was prepared by bonding an optical film 1 (a first optical film), an optical film 3 (a second optical film), and a polarizer.
[0316] (4.1.1) Preparation of water-based adhesive The following components were mixed to prepare a water-based adhesive. Pure water 100.0 parts by mass Carboxy-modified polyvinyl alcohol "Kuraray Poval (registered trademark) KL318" (Kuraray Co., Ltd.) 3.0 parts by mass Water-soluble polyamide epoxy resin "Sumirase (registered trademark) Resin 650" (aqueous solution with a solid content of 30%, manufactured by Sumika Chemtex Co., Ltd.) 1.5 parts by mass
[0317] (4.1.2) Pretreatment of the Second Optical Film The optical film 3 was immersed in a saponification treatment solution (aqueous sodium hydroxide solution at 60°C, concentration 10% by mass) for 30 seconds. Next, the optical film 3 was immersed in a water bath for 5 seconds. This was repeated twice. Thereafter, the optical film 3 was washed with a water shower for 5 seconds and then dried. The drying conditions were 70°C and 2 minutes.
[0318] Next, the optical film 3 was subjected to a swelling treatment by immersing it in water at 30° C. for 10 seconds, and then dried at 40° C. for 53 seconds.
[0319] (4.1.3) Lamination of optical film and polarizer The surfaces of the optical films 1 and 3 to be bonded to the polarizer were subjected to a corona treatment. Then, the above-mentioned aqueous adhesive was applied to the surfaces to be bonded to the polarizer, and each optical film was bonded to both sides of the polarizer. Then, the bonded laminate was immediately dried for 5 minutes in a hot air circulation dryer set at 80°C, to obtain a polarizing plate 1.
[0320] (4.2) Preparation of polarizing plates 2 to 16 Polarizing plates 2 to 16 were obtained in the same manner as in the preparation of polarizing plate 1, except that the types of the first and second optical films were changed to those shown in Tables I and II.
[0321] Tables I and II show the structures of the obtained polarizing plates. In Table II, "-" indicates that the corresponding component is not contained. "Degree of substitution" in the table indicates the degree of acetyl group substitution. The content of each additive in Table II represents the ratio of the additive to the mass of acetyl cellulose. Therefore, for example, in the case of Example 2, the content of polyester (II) is 80 mass% when converted into a ratio to the total mass of polyester (I) and polyester (II).
[0322] [Table 1]
[0323] [Table 2]
[0324] 2. Evaluation (Fabrication of Liquid Crystal Display Device) Using the polarizing plates 1 to 16 prepared above, liquid crystal display devices 1 to 16 were prepared according to the following method. The obtained liquid crystal display devices were evaluated for in-plane contrast variation and water resistance (color unevenness due to water content).
[0325] An IPS liquid crystal cell having two glass substrates with a thickness of 0.5 mm and a liquid crystal layer disposed between them was prepared. The polarizing plates 1 to 16 prepared above were then bonded together via an adhesive layer so that the second optical film was on the liquid crystal cell side, to obtain liquid crystal display devices 1 to 16. The bonding was performed so that the absorption axis of the polarizer of the polarizing plate on the viewing side (101A in FIG. 2) was perpendicular to the absorption axis of the polarizing plate on the backlight side (101B in FIG. 2).
[0326] (1) Uneven color due to water content (water resistance) The obtained liquid crystal display device was laid down on a table. "BEMCOT (registered trademark)" (manufactured by Asahi Kasei Fibers Corporation) was placed on a part of the liquid crystal display device, and the BEMCOT (registered trademark) was soaked in water. To prevent the BEMCOT (registered trademark) from drying out, the BEMCOT (registered trademark) was covered with a 100 μm thick polyester (PET) film.
[0327] A black display signal was input from the PC to the liquid crystal display device, the liquid crystal display device was turned on, and the device was left for 24 hours. The room temperature was set at 23°C, and the panel temperature at 38°C. After 24 hours, the Bemcot (registered trademark) was removed. One minute later, the L of the part of the liquid crystal display device where the Bemcot (registered trademark) had been was *The L of the water immersed part * The brightness was measured using an image colorimeter "EZ Contrast" (manufactured by ELDIM Co., Ltd.). * The L of the non-immersed part * Then, from the following formula, L * The rate of change was calculated. L * Rate of change = (L of the water immersed part * ) / (L of non-immersed part * )
[0328] The EZ contrast measurement was performed in color mode with the LCD display set to black. The water immersion conditions were that the LCD display was turned on and left to stand for 24 hours with a sheet of Bemcot (registered trademark) sufficiently soaked in water attached. L * L * a * b * Represents lightness in color space.
[0329] L * The rate of change was evaluated according to the following criteria: B or higher (A and B) was deemed to be acceptable for practical use. AA:L * The rate of change is 1.05 or less. A:L * The rate of change is greater than 1.05 and less than or equal to 1.30. B:L * The rate of change is greater than 1.30 and less than or equal to 1.55. C:L * The rate of change is greater than 1.55.
[0330] In addition, for the evaluations AA and A, the L of the water-immersed and non-immersed parts was * In evaluation B, the difference in the L between the water-immersed and non-immersed areas was * Although some color unevenness due to changes in temperature was observed, this did not pose a problem in practical use. * The color unevenness caused by the change in the color temperature was observed, which was problematic in practical use. *When the rate of change exceeded 1.80, strong color unevenness was observed.
[0331] (2) Variation in contrast The backlight of the obtained liquid crystal display device was continuously turned on for 1 hour under an environment of 23° C. and 55% RH, and then the front contrast was measured. The front contrast was measured according to the following procedure.
[0332] i) The front luminance of the display screen when the liquid crystal display device was made to display white was measured using "EZ-Contrast160D" (manufactured by ELDIM). Here, "front luminance" refers to the luminance measured from the normal direction of the display screen. Using the same method, the front luminance of the display screen when the liquid crystal display device was made to display black was measured.
[0333] ii) The ratio of the front luminance of the display screen when white is displayed to the front luminance of the display screen when black is displayed was defined as the front contrast. Front contrast = (front brightness when white is displayed) / (front brightness when black is displayed)
[0334] The front contrast was measured at nine points on the display screen of the liquid crystal display device. The nine points on the display screen were the center point of the display device and eight other points, as shown in FIG. 3. Four of the other eight points were points on the diagonal of the display device. The distance from each point to the four corners (A to D) of the display device was 1 / 10 of the length of the diagonal. The remaining four points were points on lines that bisected the display device vertically and horizontally, respectively, and these bisectors were lines that passed through the midpoints (E to H) of the four sides of the display device. The distance from the midpoints (E to H) of the four sides of the display device to each point was 1 / 10 of the length of the bisector.
[0335] The average front contrast value of the nine points was calculated. The maximum front contrast value with the largest difference from the average was also calculated. The variation in front contrast [%] was calculated using the following formula.
[0336] Front contrast variation [%] = {(maximum front contrast value) - (average front contrast value)} / (average front contrast value) x 100
[0337] The variation in front contrast was evaluated according to the following criteria: B or higher (AA to B) was deemed to be acceptable for practical use. AA: The variation in front contrast is less than 1%. A: The variation in front contrast is 1% or more and less than 5%. B: The variation in front contrast is 5% or more and less than 10%. C: The variation in front contrast is 10% or more.
[0338] In addition, in the case of the evaluation AA, no unevenness due to the variation in the front contrast was observed. In the case of the evaluation A, small unevenness due to the variation in the front contrast was observed, but it was not a problem in practical use. In the evaluation B, some unevenness due to the variation in the front contrast was observed, but it was not a problem in practical use. In the evaluation C, large unevenness due to the variation in the front contrast was observed, which was a problem in practical use.
[0339] The evaluation results are shown in Table III. In the table, "-" indicates that light leakage occurred and measurement was not possible.
[0340] [Table 3]
[0341] From the examples and comparative examples, it is understood that the polarizing plate of the present invention can suppress color unevenness and contrast variation caused by moisture content, and improves the visibility of a display device.
[0342] From Examples 1, 2, 11 and 12, it is seen that color unevenness can be further suppressed by setting the content of polyester (II) within the range of 70 to 90 mass % based on the total mass of polyester (I) and polyester (II).
[0343] From Examples 1 and 3, it is seen that by further containing polyester (III), color unevenness can be further suppressed.
[0344] It is seen from Examples 1 and 8 to 10 that the variation in contrast can be further suppressed by setting the width of the second optical film within the range of 2.2 to 3.0 m. [Explanation of symbols]
[0345] 1 Polarizing plate 2. First Optical Film 4 Polarizer 5. Second Optical Film 100 display device 101A, 101B Polarizing plate 101C Liquid crystal cell 102A, 102B First optical film 103A, 103B, 103C, 103D adhesive layer 104A, 104B polarizer 105A, 105B Second optical film 106 Adhesive layer 107 Liquid crystal layer 108A, 108B Glass substrate
Claims
1. A polarizing plate comprising a first optical film, a polarizer, and a second optical film in this order, the first optical film contains polyester, The second optical film contains a polyester represented by the following general formula (I), a polyester represented by the following general formula (II), and an acetyl cellulose having a degree of substitution of an acetyl group in the range of 2.30 to 2.80: A polarizing plate characterized by: General formula (I): T-(D-P) n -D General formula (II): T-(D-P) n -D-T In the above general formulas (I) and (II), T represents a benzene carboxylic acid residue. D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms. P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms, or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms. n represents an integer of 1 or more.
2. The content of the polyester represented by the general formula (II) is within a range of 70 to 90% by mass based on the total mass of the polyester represented by the general formula (I) and the polyester represented by the general formula (II).
2. The polarizing plate according to claim 1.
3. The polyester contained in the first optical film is polyethylene terephthalate.
2. The polarizing plate according to claim 1.
4. The second optical film further contains an ester represented by the following general formula (III):
2. The polarizing plate according to claim 1. General formula (III): T-D
5. The width of the second optical film is within a range of 2.2 to 3.0 m.
2. The polarizing plate according to claim 1.
6. A method for producing the polarizing plate according to any one of claims 1 to 5. The method for producing a polarizing plate according to the present invention comprises the steps of:
7. The polarizing plate according to any one of claims 1 to 5 is provided. The second optical film is disposed on the liquid crystal cell side. A display device comprising:
Citation Information
Patent Citations
Modifier for cellulose ester resin and film containing the same
JP2006282987A
Polyester-based modifier composition for cellulose ester resin, cellulose ester optical film, and protective film for polarizing plate
WO2014115709A1
Phase difference film, polarization plate and liquid crystal display device
WO2015060167A1
Polarizing plate protective film, production method therefor, polarizing plate, and liquid crystal display device
WO2016111316A1
Polarizing plate and liquid crystal display device
WO2018070131A1
Cited By
Conductive film-equipped substrate, electronic device, electromagnetic wave shielding sheet, planar heating element, and method for manufacturing conductive film-equipped substrate
WO2026205157A1